Development and optimization of antifungal nanoemulsion of lemongrass (Cymbopogon citratus) essential oil using central composite rotatable design - Larissa G.R. Duarte; Josemar G. de Oliveira Filho; Conny W.T. Fukuyama; Isadora C. Pedrino; Ygor G.P. Osti; Milene C. Mitsuyuki; Marcos David Ferreira (Food and Humanity, 2026)

Quantity vs. quality: divergent carbon stabilization pathways under eucalyptus and natural succession - Cintia Dayrane Duarte Moreira; Murilo Ferre de Mello; Gustavo de Oliveira Alves; Eric Batista Ferreira; Marcos Rogério Tótola; Teogenes Senna de Oliveira (CATENA, 2026)

Ecotoxicity and recovery of Poecilia reticulata exposed to cosmetic effluent, graphene oxide, iron oxide nanoparticles and magnetic graphene oxide - Walter de Souza Rodrigues; João Marcos de Lima Faria; Diego Stéfani Teodoro Martinez; Theodoro da Rosa Salles; Victoria Costa da Silva; Débora dos Santos Pereira; Ryan Marques Rezende; Ana Luiza Torres Soares; Isabela Cristina Louza Goulart; Jordana Duarte de Souza; Lucas Camilo Moraes Alves; Simone Maria Teixeira de Sabóia-Morais (Aquatic Toxicology, 2026)

Biological parameters of Rhipicephalus linnaei determined using rabbits as experimental hosts under laboratory conditions - Joelly Santos; Marcos Valerio Garcia; Pâmella Oliveira Duarte; Leandra Marla Oshiro; Leandro de Higa; Álvaro Aragão; Jinávila Dandara de Rocha; Jacqueline Cavalcante Barros; Renato Andreotti (Experimental and Applied Acarology, 2026)
Rhipicephalus linnaei is a tick widely associated with domestic dogs and is of recognized veterinary and public health importance. However, the recent taxonomic delimitation of this species, previously included within the Rhipicephalus sanguineus sensu lato complex, has made the production of species-specific biological data necessary. Therefore, this study aimed to characterize the life cycle parameters and reproductive performance of R. linnaei under controlled laboratory conditions. The specimens used were obtained from a laboratory colony established from engorged females collected from dogs, and artificial infestations were subsequently performed on rabbits. We evaluated the engorgement periods in larvae, nymphs, and adults; the molting period in the immature stage; and, in adult females, the body weight, preoviposition period, egg mass weight, incubation period, hatching rate, and nutritional conversion index. The results revealed significant differences among developmental stages, with an increase in the engorgement period from the larval stage to the adult stage and a longer molting period in the nymph stage. In adult females, a strong positive association was observed between body weight and egg mass weight, indicating a direct relationship between blood meal volume and reproductive investment. In addition, heavier egg masses were associated with higher hatching rates. These results provide updated information on the biology of R. linnaei and contribute to a more precise understanding of its dynamics under the currently accepted taxonomy.

Climate extremes, WASH deficits, and infectious diseases in the Brazilian Amazon: Insights from explainable machine learning (2010−2022) - Ana Karoline Duarte dos Santos Sá; Marco Valerio Jansen Cutrim; Rafael Diego Barbosa Soares; Quedyane Silva da Cruz; Andrea Christina Gomes de Azevedo Cutrim; Yago Bruno Silveira Nunes; Paulo Henrique Rocha Aride; Jeniffer Hachiley de Sousa Torquato; Antonio Ronnilson Dias Carneiro Sá (Science of The Total Environment, 2026)

Functional redundancy and structural flexibility as contrasting plankton strategies under macrotidal pulses - Quedyane Silva da Cruz; Marco Valério Jansen Cutrim; Pedro Augusto Mendes de Castro Melo; Ana Karoline Duarte dos Santos Sá; Yago Bruno Silveira Nunes; Bruna Oliveira Ferreira; Francisco José da Silva Dias; Vinicius Henrique Maciel dos Santos; Taiza Pimentel Santos (Marine Environmental Research, 2026)

Associations between teat apex, milk microbiota, and udder health in primiparous cows: Effects of decontamination in a low biomass context - José A. Ferronatto; Eduardo M. Ramos-Sanchez; Erika K. Ganda; Marcos B. Heinemann; Juliano L. Gonçalves; Marcos V. dos Santos; Julia A. Arantes; Vinicius S. Duarte; Alessandro S. Guimarães; Marcio C. Costa; Marie Joossens; Sarne De Vliegher; et al. (Research in Veterinary Science, 2026)

Ecosystem Services of Freshwater Swamp Forests: Mechanisms of Hydrological Regulation and Impacts of Global Environmental Change - Ana Paula Roschildt; Daniel Burd Villanova; Caroline Igansi Duarte; Saimon Branco Bueno; Marcos Antonio Bacarin; Tanise Luisa Sausen; Junior Borella (Wetlands, 2026)
Freshwater swamp forests (FSFs) are flood-prone ecosystems on nutrient-rich alluvial soils that provide important ecosystem services, yet remain underrepresented in wetland research and management. This integrative review synthesizes current knowledge on FSFs with emphasis on three interconnected themes: (i) ecological definition, classification, and hydrological dynamics; (ii) the role of microtopography and evapotranspiration in regulating water storage and fluxes; and (iii) potential responses of these coupled processes to climate change. Although the “sponge” metaphor is seldom explicitly applied to FSFs, the reviewed literature consistently shows that water retention, delayed release, and vegetation-mediated fluxes are functionally linked, albeit often studied separately. Fine-scale surface heterogeneity, particularly hummocks and depressions, emerges as a key mechanism promoting water redistribution, groundwater recharge, and the persistence of localized refugia and microhabitats. At the same time, climate change-driven shifts in precipitation, drought frequency, heat stress, and disturbance regimes may weaken these regulatory functions and reduce ecosystem resilience. We therefore propose the “sponge–pump framework” as a conceptual model linking hydrological storage (“sponge”) and vegetation-driven water fluxes (“pump”) to explain how FSFs regulate water movement, support biodiversity, and contribute to ecosystem services across spatial and temporal scales. The framework also highlights the need for standardized quantification, broader geographic coverage, and greater integration of microtopographic processes in wetland conservation, restoration, and climate adaptation strategies.

Sustainable Production and In Vitro Giardicidal Activity of Bioactive Compounds Derived from Arthrospira Platensis - Ketyline Lira de Lima; Júlia Sofia Neves de Sousa; Karina Evelyn de Lima Albuquerque Santos; Maria Rafaele Oliveira Bezerra da Silva; Raquel Pedrosa Bezerra; Romero Marcos Pedrosa Brandão Costa; Kethylen Barbara Barbosa Cardoso; Patrícia Melo Ferreira; Genésio Florentino Duarte Neto; Silvana de Fátima Ferreira; Daniela de Araújo Viana Marques (Acta Parasitologica, 2026)
Background Giardiasis remains a globally prevalent neglected parasitic disease, and limitations associated with conventional therapies highlight the need for alternative and complementary strategies. In this context, microalgae biocompounds have emerged as promising sources of antiparasitic agents. Objective This study aims to evaluate the in vitro preliminary screening activity (vital dye exclusion). Methods Aqueous extracts of Arthrospira platensis obtained by different extraction methods, as well as the bioactivity of the product derived from in vitro digestion (PDV), aiming to assess the influence of extraction and digestive bioactivation on antiparasitic efficacy. Extracts were produced by magnetic stirring and sonication, followed by exposure of Giardia duodenalis cysts to increasing concentrations, with metronidazole used as a reference drug. The PDV was generated using a standardized simulated gastrointestinal digestion model. Sonicated extracts showed enhanced membrane damage compared to mechanically stirred extracts, consistent with improved release of intracellular bioactive compounds. The IC 50 values for the sonicated, agitated, and PDV samples were, respectively: 95,4; 153.1 and 43.6 μg/mL. Results The PDV demonstrated activity across multiple concentrations and, under comparable conditions, outperformed metronidazole. These findings suggest that digestive processing may increase the bioaccessibility of active moieties responsible for antiparasitic effects. Conclusions Overall, the results support A. platensis as a sustainable source of giardicidal biocompounds and highlight the relevance of physiologically relevant in vitro digestion models for predicting functional antiparasitic activity and guiding future translational research.

Blue carbon inventories of Spain and Portugal for their inclusion in national climate mitigation strategies - Nerea Piñeiro-Juncal; Oscar Serrano; Carmen B. de los Santos; Nuria Marbà; Elena Díaz-Almela; Fernando Tuya; Inés Mazarrasa; Joxe Mikel Garmendia; Xosé Lois Otero; Karina Inostroza; Jordi F. Pagès; Gonzalo Mendez-Martínez; et al. (Marine Pollution Bulletin, 2026)

Methane mitigation, nutritional evaluation, and in vitro degradation kinetics of diets based on tropical grass haylage treated with xylanase - Ana Beatriz de Almeida Duarte; Tairon Pannunzio Dias-Silva; Wesleyson Cristian Correa Viana; Antonio Leandro Chaves Gurgel; Marcos Jácome de Araújo; Adibe Luiz Abdalla; Leílson Rocha Bezerra; Ricardo Loiola Edvan; Romilda Rodrigues Nascimento; Sheila Vilarindo de Sousa; Carlo Aldrovandi Torreão Marques; Luis Carlos Vinhas Ítavo; et al. (Tropical Animal Health and Production, 2026)
The aim of this study was to evaluate the effect of xylanase addition (1.8 g/kg dry matter [DM]) to tropical grass haylage used in total mixed rations (TMR) on in vitro organic matter degradability, ruminal fermentation kinetics, and methane (CH4) emission. A completely randomized design was adopted in a 4 × 2 factorial arrangement, corresponding to four tropical grass cultivars (Andropogon, Mombaça, Massai, and Marandu) with or without xylanase addition and five replications per treatment (haylage bales), totaling 40 experimental bales. Ninety days after baling, the bales were opened and used to formulate total mixed rations, which were used as substrates for the in vitro incubations, according to the experimental treatments, totaling 40 TMR units (experimental diets). Chemical composition and ruminal fermentation parameters differed among grass cultivars. TMR based on Andropogon haylage showed greater crude protein concentration and higher acetate production ( P < 0.0001), whereas Mombaça haylage promoted greater propionate production and a more favorable acetate: propionate ratio ( P < 0.0003). The addition of xylanase did not alter organic matter degradability or total gas production ( P > 0.05). However, xylanase tended to reduce CH4 emission ( P = 0.0882) and improve CH4 efficiency ( P = 0.0701), indicating a potential mitigation effect on enteric methane production. Diets based on Massai haylage without xylanase showed lower gas production and faster fractional fermentation rates. Overall, the results indicate that tropical grass haylage can be successfully used in TMR systems, and xylanase supplementation may contribute to improved ruminal fermentation efficiency and methane mitigation, although further studies evaluating different enzyme levels are still required.

Nutritional Efficiency for Fertigated Sugarcane Varieties Under Deficit Irrigation Strategies - Nathália Lopes Ribeiro; Rubens Duarte Coelho; Fernando da Silva Barbosa; Lucas da Costa Santos; Daniel Philipe Veloso Leal; Jonathan Vásquez Lizcano; Eusímio Felisbino Fraga Júnior; Timóteo Herculino da Silva Barros; Marcos Antonio Correa Matos do Amaral; Jéfferson de Oliveira Costa (Irrigation and Drainage, 2026)
Among the many factors that limit sugarcane crop yield, the precise supply of nutrients and water under drip irrigation systems can be the shortcut to higher yields in the field. This research aimed to evaluate the nutritional efficiency of fertigated sugarcane varieties under deficit irrigation strategies. The experiment was conducted in a rain‐out shelter with the soil type Oxisol Typic Ustox. The experimental design adopted was randomized blocks, with three complete blocks. The treatments were distributed in a factorial scheme (4 × 8), totalling 32 treatments and 96 experimental plots. Four irrigation strategies and eight commercial sugarcane varieties (CTC15, CTC17, RB867515, RB92579, RB931011, RB966928, IAC5000 and NCo376) were studied. Leaf, sheath, pointer and stalk samples were ground for determination of macronutrient and micronutrient contents. All the nutrients had greater quantities allocated to the stalk. The CTC15 variety accumulated a greater quantity of nutrients and was more efficient in terms of gross sugar yield, whereas RB966928 was more efficient in terms of the production of total recoverable sugars and the production of apparent sucrose. The 100% irrigation level provided greater accumulation of nutrients in the aboveground parts, whereas the 50% irrigation level resulted in higher values of nutrient use efficiency.

Himatanthus drasticus (Mart.) Plumel (APOCYNACEAE): phytochemical profile, evaluation of antibacterial and drug-potentiating activity, and toxicity of stem bark extracts - Maraiza Gregorio de Oliveira; Adrielle Rodrigues Costa; Jailson Renato de Lima Silva; Carlos Alonso leite dos Santos; Ana Raquel Pereira da Silva; Daniel Sampaio Alves; José Weverton Almeida-Bezerra; Ademar Maia Filho; José Walber Gonçalves Castro; Bárbara Fernandes Melo; Francisca de Fátima Silva de Sousa; Marcos Santos; et al. (Vegetos, 2026)

Spatio-temporal dynamics of water quality during and after an extreme flood event in southern Brazil - Lucas Bohnenberger; Marcos Henrique Gomes Ribeiro; Luana Morais da Rosa; Cláudia Soares Pereira da Silva; Vinícius Duarte Soroka; Louidi Lauer Albornoz; Lucia Helena Ribeiro Rodrigues; Salatiel Wohlmuth da Silva (Science of The Total Environment, 2026)

Microplastic Pollution in Water and Sediments in a Public Supply Reservoir in Presidente Prudente (SP), Brazil - Marco Antonio Saraiva da Silva; Guilherme Dognani; Leonardo Cruz Mendes da Silva; André Luiz Lopes de Faria; José Tadeu Garcia Tommaselli; João Osvaldo Rodrigues Nunes; Eduardo Nery Duarte de Araujo; Carlos José Leopoldo Constantino; Mitchael Micael Silva Gomes (Water, Air, & Soil Pollution, 2026)
Herein, we investigate the occurrence, distribution, polymer composition, and abundance of microplastics in water and sediment samples collected from the Sabesp reservoir in Presidente Prudente, São Paulo State, Brazil, a major source of public water supply. Sampling was conducted at six points during three distinct campaigns to assess seasonal and spatial variations. A total of 663 microplastic particles were identified (636 in water and 27 in sediment), predominantly fibers (78% in water and 48% in sediment). The main polymers identified by micro-Raman spectroscopy were PET, PP, PES, PE, and iPP, along with fibers showing spectral signatures of indigo dye. Higher microplastic concentrations were observed near the spillway, likely influenced by hydrological flow dynamics and proximity to urbanized areas, suggesting that untreated domestic and industrial effluents are the primary sources of contamination. Based on the reservoir volume and sample data, the total estimated microplastic load was approximately 15.7 million particles. The persistence of these materials, combined with their potential to adsorb other pollutants, poses significant environmental and human health risks. These findings underscore the need for continuous water-quality monitoring, improved waste management, and effective public policies aimed at reducing plastic inputs into aquatic environments, contributing to the global effort to mitigate microplastic pollution.

Valorization of Fruit Peel Waste via Microwave-Assisted Co-Pyrolysis: Dual-Optimized Biochar Production for Soil Amendment and Pollutant Adsorption - Calton J. Dinis; Reginaldo J. Cavallaro; Lúcio V. C. Girão; Claudio R. Duarte; Marcos A.S. Barrozo (BioEnergy Research, 2026)
The valorization of fruit peel waste through microwave-assisted co-pyrolysis (MACP) offers a sustainable pathway for producing high-performance functional materials. This study employed a Central Composite Design (CCD) and multi-objective desirability function to engineer biochars tailored for soil amendment (BCop-bf) and pollutant adsorption (BCop-ads). Synergistic effect analysis provided empirical evidence of the superiority of biomass blending, showing significant gains in nitrogen (15.77%), phosphorus (14.29%), and oxygen-containing functional groups (15.44%) compared to theoretical additive values. Optimization for BCop-bf (212.3 °C) maximized macronutrient retention (7.93% N, 7.62% K), while BCop-ads (259.4 °C) yielded a matrix with high surface functionality (3.44 mmol/g of OFG). Thermogravimetric analysis (TGA/DTG) of the optimized products confirmed high thermal recalcitrance, with residual masses exceeding 50% at 800 °C, ensuring long-term carbon stability. Although the BET surface area was modest (10.84 m²/g), textural analysis revealed a predominantly mesoporous structure (pore size of 2.94 nm) that, combined with a versatile point of zero charge (pHpzc = 8.0), facilitates mass transfer and multi-mechanism adsorption. This dual-optimization strategy validates MACP as a robust technology for converting environmental liabilities into application-specific resources for the circular bioeconomy.

First report of Colletotrichum fructicola causing anthracnose on Lippia alba in Brazil - André Nunes de Oliveira; Ana Gabriele Gurgel Amaral; Ingrid Gomes Duarte; Bruno Leonardo Mendes; Lavinia Gabriely de Albuquerque Freitas; Rosana Blawid; Paolo Margaria; Marcos Paz Saraiva Câmara (Journal of Plant Pathology, 2026)

Assessment of Methane Production and Microbial Community Dynamics in One and Two-Stage Semi-continuous Anaerobic Systems Treating Orange Peel Waste and Crude Glycerol - Maria Teresa de Jesus Camelo Guedes; Marcos Henrique Gomes Ribeiro; Vinícius Duarte Soroka; Karen Karine da Rosa Dias; Jeverson Frazzon; Maria Cristina de Almeida Silva (BioEnergy Research, 2026)
Agro-industrial wastes such as orange peel waste (OPW) and crude glycerol (CG) can be used in anaerobic digestion (AD) to mitigate environmental impacts while generating methane as a renewable biofuel. Brazil produces significant amounts of these residues, highlighting the need for sustainable management strategies. This study evaluated the performance of single and two-stage anaerobic systems in the co-digestion of OPW and CG under mesophilic conditions (35–37 °C) for 60 days, with increasing organic loading rate (OLR). The two-stage system achieved higher cumulative methane yields (2703 NmL CH₄/gVS) compared to the single-stage system (2012 NmL CH₄/gVS). However, in the two-stage configuration, the acidogenic stage was associated with a pronounced accumulation of VFAs in the methanogenic reactor (SCM2), reaching concentrations up to 60,000 mg/L, which negatively affected methane production, despite the absence of detectable D-limonene inhibition. Additionally, increasing the OLR by 20% and the daily addition of alkalizing agents to control pH were detrimental to methane generation. Microbial analysis revealed the predominance of hydrolytic and acidogenic genera after day 29, such as Enterobacter (16% in SCM1 and 3% in SCM2), Proteiniphilum (35% in SCM1 and 27% in SCM2), and Fermentimonas (48% in SCM2 on day 60), indicating an incomplete methanogenic phase. Overall, the results suggest that, under the evaluated conditions, the inclusion of an acidogenic stage upstream of methanogenesis did not result in a clear enhancement of methane production.

Seasonal bottom-up and top-down control of plankton in a hypereutrophic macrotidal lagoon on Brazil’s equatorial coast - Marco Valério Jansen Cutrim; Yago Bruno Silveira Nunes; Ana Karoline Duarte dos Santos Sá; Quedyane Silva da Cruz; Andrea Christina Gomes de Azevedo-Cutrim; Jordana Adorno Furtado (Environmental Monitoring and Assessment, 2026)
Tropical coastal lagoons often show pronounced seasonal forcing that modulates nutrient supply, light climate, and grazer pressure. We surveyed hypereutrophic Jansen Lagoon (São Luís Island, Brazil) in four campaigns during 2017 (rainy: March and April; dry: September and November) at nine near-surface stations sampled on ebb tide. Phytoplankton and zooplankton were collected and analyzed together with chlorophyll-a and nutrients to assess short-term community responses. Clustering and nMDS revealed clear rainy–dry segregation of communities, and dbRDA linked dry-season samples to higher salinity, turbidity, TP, and silicate, whereas rainy-season samples were associated with higher dissolved oxygen, Secchi depth, ammonium, and DIN. Generalized linear models explained 65% of phytoplankton variance: density increased with DIP and decreased with dissolved oxygen and with the rotifer Filinia longiseta , indicating concurrent bottom-up (nutrients, light/renewal) and top-down (grazing) controls. Microcystis wesenbergii and M. aeruginosa exhibited frequent peaks, underscoring eutrophic risk, though values remained below the bloom threshold applied here. Overall, bottom-up control predominated in the rainy season, whereas grazer pressure intensified in the dry season. Management should couple nutrient-load reductions with measures that shorten residence time, reduce resuspension, and restore macrophytes, with priority to urban margins and semi-enclosed embayments; routine tracking of DO percent saturation, DIN/DIP, Secchi depth, and chlorophyll-a is recommended for long-term assessment.

Inoculation with Bacillus subtilis and Paenibacillus sp. shapes the rhizosphere bacteriome of prickly pear cactus under water deficit - Rhaiana Oliveira de Aviz; Janaira Rocha Campos; Marcos Renan Lima Leite; Sandra Mara Barbosa Rocha; Maria Helena Ferreira Duarte; Pâmalla Graziely Carvalho Moraes; Gonçalves Albino Dauala; Elaine Martins da Costa; Rafael de Souza Miranda; Cacio Luiz Boechat; Arthur Prudêncio de Araujo Pereira; Erika Valente de Medeiros; et al. (Plant and Soil, 2026)
Background and aims Prickly pear cactus ( Nopalea cochenillifera L.) plays a central role in sustaining forage production in semiarid environments, yet prolonged drought associated with climate change increasingly constrains its performance. Plant growth-promoting bacteria (PGPB), including Bacillus subtilis and Paenibacillus spp., are recognized for enhancing plant tolerance to water limitation, but their influence on the rhizosphere microbiome of cactus under drought conditions remains unclear. We tested whether inoculation with these bacteria shapes rhizosphere bacterial community composition and interaction patterns under water deficit. Methods A greenhouse experiment was conducted using a factorial design combining two water regimes (well-watered and water-deficit) with three inoculation treatments ( B. subtilis , Paenibacillus sp., and a non-inoculated control). After 150 days of water stress exposure, rhizosphere bacterial communities were assessed using 16S rRNA gene amplicon sequencing. Results Water availability was the dominant driver of rhizosphere bacterial community structure, with drought favoring Actinobacteriota and well-watered conditions enriching Proteobacteria. Inoculation with B. subtilis modified community composition and increased the prevalence of drought-associated taxa, while also promoting a higher proportion of positive microbial interactions under water deficit. In contrast, Paenibacillus sp. exerted weaker and more variable effects. Despite microbial shifts, inoculation did not significantly affect plant biomass or root traits. Conclusions Rhizosphere bacterial communities of prickly pear cactus are primarily structured by water availability, whereas PGPB inoculation induces secondary, taxa-specific effects. Under drought, B. subtilis enhances microbial network connectivity, suggesting that inoculants may influence rhizosphere functioning even when plant growth responses are limited.

Evaluation of Anaerobic Digestion of Antibiotics in Batch Reactors: Effect on Methane and Biogas Production, Operating Parameters and Aqueous Phase Removal Efficiency - Marcos Henrique Gomes Ribeiro; Vinicius Duarte Soroka; Odorico Konrad; Maria Cristina de Almeida Silva; Antônio Domingues Benetti (International Journal of Environmental Research, 2026)

High meiofaunal diversity in the Azores revealed through DNA metabarcoding - Francesca Leasi; Nuno V. Álvaro; Luiz F. Andrade; Thiago Q. Araújo; Víctor Aramayo; Tom Artois; Will M. Ballentine; Franziska S. Bergmeier; Andrea Z. Botelho; Ariane Buckenmeyer; Ana T. Capucho; Irina Cherneva; et al. (Marine Biodiversity, 2026)
To advance understanding of meiofauna, key components of marine benthic ecosystems, an international team conducted a morphology-based taxonomic survey and workshop around São Miguel, the largest Azorean island, in 2019. The survey yielded critical baseline data on meiofaunal diversity and, despite taxonomic challenges that limited identification of certain taxa, laid a solid foundation for further research. To expand these findings, additional samples were analyzed using DNA metabarcoding, a powerful tool that assesses multiple facets of biodiversity, including richness, community composition, and phylogenetic diversity. Metabarcoding identified 480 meiofaunal amplicon sequence variants across 14 phyla, more than doubling the 180 taxa recorded through morphology alone. Of these, 298 (approximately 62%) belonged to phyla targeted during the morphology-based workshop. A comparison between the two approaches, focusing on clades addressed during the workshop, revealed overlapping but expanded patterns of diversity relative to morphology-based taxonomy. This consistency supports the metabarcoding’s ability to uncover meiofaunal diversity and underscores the importance of integrating both methods to achieve a more comprehensive understanding of biodiversity and ecological patterns. As the first metabarcoding study in the Azores, this work establishes a biodiversity baseline for a remote and understudied region, indicating greater benthic diversity than previously recognized. By revealing the complexity of these understudied ecosystems, this research contributes to document and support conservation of biodiversity in the Azores and emphasizes the need for further exploration of meiofaunal communities in isolated oceanic environments.

Unveiling the hidden consequences of mining tailings on ecosystem processes: Disruption of decomposition of native species in the Rio Doce watershed - João Carlos Figueiredo; Yule Roberta Ferreira Nunes; Walisson Kenedy-Siqueira; Renata Maia; Yumi Oki; Milton Barbosa; Débora Lima-Santos; Flávio Mariano Machado Mota; Daniel Negreiros; Letícia Ramos; Marcos Paulo dos Santos; Rebeca Ferreira Reis; et al. (Forest Ecology and Management, 2026)

Growth stage as the main drive over genotype and plant growth-promoting bacteria on bacterial communities in the rhizosphere of prickly-pear cactus - Rhaiana Oliveira de Aviz; Janaira Rocha Campos; Davila Esmelinda Oliveira Silva; Mayanna Karlla Lima Costa; Marcos Renan Lima Leite; Sandra Mara Barbosa Rocha; Pâmalla Graziely Carvalho Morais; Gonçalves Albino Dauala; Maria Helena Ferreira Duarte; Cacio Luiz Boechat; Rafael de Souza Miranda; Elaine Martins da Costa; et al. (Applied Soil Ecology, 2026)

Responses of aquatic communities to seasonal changes in a non-perennial river of the Brazilian semiarid region - Milena Gonçalves-Silva; Thibault Datry; Marcos Adelino Almeida Filho; Maria Rita Nascimento Duarte; Camila Rabelo Oliveira Leal; Tamara Maciel Pereira; Victor Satoru Saito; Andros T. Gianuca; Carla Ferreira Rezende (Aquatic Sciences, 2026)

Out of sight, but not out of mind: Key issues regarding seafloor macrolitter monitoring - Georg Hanke; Miquel Canals; Ryota Nakajima; Melanie Bergmann; Francois Galgani; Daoji Li; George Papatheodorou; Christopher Kim Pham; Diva J. Amon; Michela Angiolillo; Lene Buhl-Mortensen; Alessandro Cau; et al. (Marine Pollution Bulletin, 2025)

Fatal Bothrops atrox snakebite with thrombotic microangiopathy, hemorrhagic stroke and acute kidney injury - Larissa Rocha Alípio Duarte; Érica Carvalho; Tigran Francis Chehuan Melo; Fabiane Bianca Albuquerque Barbosa; Rosilene Viana de Andrade; Marco Sartim; Felipe Queiroz Araújo; Jacqueline Sachett; Guilherme Pivoto; Luiz Carlos de Lima Ferreira; Wuelton Monteiro (Toxicon, 2025)

Bacillus and Paenibacillus Strains Enhance Nitrogen Metabolism and Increase Biomass Production of Nopalea Cochenillifera Grown in semi-arid Soil - Acacyara Batista de Sousa; Marcos Renan Lima Leite; Gonçalves Albino Dauala; Pâmalla Graziely Carvalho Morais; Stelamaris de Oliveira Paula Marinho; Gilnair Nunes Monteiro; Maria Helena Ferreira Duarte; Ruthanna Isabelle de Oliveira; Rodrigo Fonseca da Silva; Rhaiana Oliveira de Aviz; Rafael de Souza Miranda; Cácio Luiz Boechat; et al. (Journal of Soil Science and Plant Nutrition, 2025)

Fertility and carbon stocks in Oxisols under Urochloa pastures and Eucalyptus-based agrosilvopastoral systems established in the Brazilian Cerrado - Jaqueline de Cássia de Oliveira; Igor Costa de Freitas; Ana Clara Santos Duarte; João Gabriel Figueiredo Moreira; Alex José Silva Couto; Marcos Fernando Gonçalves Lessa; Miguel Marques Gontijo Neto; Márcia Vitória Santos; Mauricio Roberto Cherubin; Carlos Eduardo Pellegrino Cerri; Leidivan Almeida Frazão (Soil and Tillage Research, 2025)

Decoding climate-induced phytoplankton dynamics in a tropical macrotidal estuary using explainable machine learning - Ana Karoline Duarte dos Santos Sá; Marco Valério Jansen Cutrim; Quedyane Silva da Cruz; Ricardo Luvizotto-Santos; Andrea Christina Gomes de Azevedo-Cutrim; Yago Bruno Silveira Nunes; Bruna Oliveira Ferreira; Antonio Ronnilson Dias Carneiro Sá (Science of The Total Environment, 2025)

Dynamics of phytoplankton functional groups and carbon concentrations in an estuary on the Brazilian equatorial margin - Danielle Stephane Campos Souza; Andrea Christina Gomes de Azevedo-Cutrim; Ana Karoline Duarte dos Santos Sá; Marco Valério Jansen Cutrim; Ana Virgínia Gomes de Oliveira; Quedyane Silva da Cruz; Rayane Serra Rosas; Christyélen Campos Souza (Marine Environmental Research, 2025)

Functional diversity and spatial distribution of zooplankton communities on the Maranhão continental shelf, Brazilian equatorial Atlantic - Yago Bruno Silveira Nunes; Marco Valério Jansen Cutrim; Xiomara Franchesca Garcia Dias; Nuno Filipe Alves Correia de Melo; Ana Karoline Duarte dos Santos Sá; Quedyane Silva da Cruz (Marine Environmental Research, 2025)

Projected cooling and pCO2 conditions in upwelling zones and their influence on a prominent rocky shore ecosystem engineer - Nicole Jahnsen-Guzmán; Nelson A. Lagos; Marco A. Lardies; Pedro A. Quijón; Diego Quintanilla-Ahumada; M. Roberto García-Huidobro; Claudio García; Nicol Zúñiga-Cueto; Cristian Duarte (Estuarine, Coastal and Shelf Science, 2025)

The biological potential and health-benefits of flavonoids: A review and development opportunities - Marco Duarte; Sílvia Santos Pedrosa; P Raaj Khusial; Ana Raquel Madureira (Chemico-Biological Interactions, 2025)

Effect of shrimp head lipid extract on growth, body composition, tissue and feed antioxidant parameters, and serum profile of nile tilapia (Oreochromis niloticus) - Guilherme Melgaço Heluy; Maria Angélica da Silva; Vivian Costa Vasconcelos; Gerlayne Maria dos Santos; Josiane Ramos da Silva; Marcele Trajano de Araújo; Thiago Barbosa Cahú; Bruno Oliveira de Veras; Leucio Duarte Vieira Filho; Romero Marcos Pedrosa Brandão Costa; Ronaldo Olivera Cavalli; Maria do Carmo Mohaupt Marques Ludke; et al. (Tropical Animal Health and Production, 2025)

Sex Drives Intraspecific Scaling of Home Range Size in Mammals - Aline Giroux; Denis Valle; Eliezer Gurarie; Marcus Vinicius Vieira; James D. Forester; Luca Börger; Raissa Sepulvida; Nicole Barbour; Erika G. da Rocha; Julia Oshima; Fernanda C. de Azevedo; Frederico G. Lemos; et al. (Ecology Letters, 2025)
Understanding variation in home range size (HR) provides important insights into the underlying ecological processes driving space use. However, it remains unclear whether the interspecific allometric scaling of mammals' HR can also be consistently observed within species and for both sexes. To address this knowledge gap, we GPS‐tracked 349 resident individuals across Brazil, encompassing 18 mammal species. We estimated individuals' HR and modelled intraspecific variation in HR against body mass (BM) and sex. While males showed a positive allometric scaling similar to interspecific findings reported in the literature (exponent = 1.23), females' BM had no statistically discernible relationship with HR. We suggest that males have greater energetic and evolutionary incentives to expand their HR with increasing BM, and more physical capacity to do so. Traditional studies on HR scaling that disregard individual sex may, in reality, reflect an average of two distinct patterns, while failing to accurately represent either one.

Corrigendum to “Evaluation of the toxic and genotoxic effects of exposure of Drosophila melanogaster to the glutathione-capped AgIn5Se8@ZnS nanocrystals” [Chemosphere, (2025), vol. 381, pages 144482] - Antônio Marcos de Oliveira dos Santos; Danilo Gustavo Rodrigues Silva; Maria Gislaine Pereira; Adrielle Rodrigues Costa; Claudia Rohde; Camila Caroline Lopes Arruda; Antônia Eliene Duarte; Lizandra Ferraz da Silva; Denilson Vasconcelos Freitas; Marcelo Navarro; Maríndia Deprá; Daniela Maria do Amaral Ferraz Navarro; et al. (Chemosphere, 2025)

Conversion of brewery spent grain into 2,3-butanediol: A sustainable approach using biomass treatments - Daniele Misturini Rossi; Estela Marisutti; Clarissa Izabel Silveira Costa; Estela Moschetta Eidelwein; Bruno Marques Viegas; Lilian Raquel Hickert; Suse Botelho da Silva; Lovaine Silva Duarte; Marco Antônio Záchia Ayub (Journal of Environmental Chemical Engineering, 2025)

Biotechnological potential of pineapple-Serendipita co-cultivation for salinity resilience in agriculture - Danielle da Silva; Ana Kelly de Sousa Silva; Fernanda Vidigal Duarte Souza; Yohan Fritsche; Valdir Marcos Stefenon (Plant Cell, Tissue and Organ Culture (PCTOC), 2025)

Late Quaternary population expansion in gray brocket deer [ Subulo gouazoubira (G. Fisher, 1814), Cervidae, Mammalia] in Brazil - Alex Hubbe; Mark Hubbe; Elver Luiz Mayer; Eliane Nunes Chim; Paulo Miguel Haddad‐Martim; Augusto S. Auler; Luís B. Piló; William J. Pestle; Alba Rey‐Iglesia; Isac dos Santos Antônio Machado; Paulo C. F. Giannini; Eluzai Dinai Pinto Sandoval; et al. (Journal of Quaternary Science, 2025)
There is little information about the changes in the abundance of mammalian species in South America during the late Quaternary, which is a key parameter to understanding past ecological and evolutionary dynamics. Here, we describe a conspicuous increase in the abundance of the gray brocket deer ( Subulo gouazoubira G. Fisher, 1814; Mammalia) during the late Quaternary in Brazil based on paleontological evidence. We studied the material retrieved from pitfall deposits in Cuvieri Cave (Brazil) representing three time intervals (Late Pleistocene, Pleistocene/Holocene transition, and Holocene). The deposits in this cave were previously characterized in terms of facies composition, chronology, and overall taxa and taphonomy. We combined previous data with taxonomic identification at the species level for deer (morphological and ancient DNA analyses), quantification of the number of individuals for large mammals (>10 kg), taphonomic analyses, and stratigraphic distribution of specimens. Our results show that while in the Late Pleistocene gray brocket deer corresponded to up to 18% of 38 individuals, in the Holocene they represented at least 82% of 78 individuals. We interpret this change in frequency as a considerable increase in abundance in the surroundings of the cave, after excluding major taphonomical biases. The causes for this phenomenon are uncertain but could have involved a surplus of food availability and predation release due to the late Quaternary extinction event.

Evaluation of the toxic and genotoxic effects of exposure of Drosophila melanogaster to the glutathione-capped AgIn5Se8@ZnS nanocrystals - Antônio Marcos de Oliveira dos Santos; Danilo Gustavo Rodrigues Silva; Maria Gislaine Pereira; Adrielle Rodrigues Costa; Claudia Rohde; Camila Caroline Lopes Arruda; Antônia Eliene Duarte; Lizandra Ferraz da Silva; Denilson Vasconcelos Freitas; Marcelo Navarro; Maríndia Deprá; Daniela Maria do Amaral Ferraz Navarro; et al. (Chemosphere, 2025)

Ruminal and intestinal morphometric parameters of lambs fed diets containing Mimosa tenuiflora (Willd.) hay replacing Buffel grass hay - Mikael Leandro Duarte de Lima Tolentino; Laura Honório de Oliveira Tolentino; Larissa Maria Feitosa Gonçalves; Otávio Brilhante de Sousa; José Morais Pereira Filho; Tairon Pannunzio Dias-Silva; Antonio Leandro Chaves Gurgel; Marcos Jácome de Araújo (Small Ruminant Research, 2025)

Methods to assess on-farm biosecurity in Europe and beyond - Fernando Duarte; Lena-Mari Tamminen; Miroslav Kjosevski; Giovanna Ciaravino; Mattias Delpont; Carla Correia-Gomes; Bart H.P. van den Borne; Ilias Chantziaras; Laura Valeria Alarcón; Line Svennesen; Ina Toppari; Alessandra Piccirillo; et al. (Preventive Veterinary Medicine, 2025)

Essential oils from Lamiaceae plants effectively control Colletotrichum gloeosporioides, Elsinoë ampelina and Phytophthora infestans - Marcos Vinicius Horst; Leandro Alvarenga Santos; Adriana Knob; Elis Marina Müller Silva; Cacilda Márcia Duarte Rios Faria (Brazilian Journal of Microbiology, 2025)

Geochronology and stratigraphy of the Boa Vista de Minas Group: An example of a Meso-to Neoarchean greenstone-belt in amphibolite-to granulite-facies - Renato de Assis Barros; Renato Moraes; Marco Aurélio Piacentini Pinheiro; Ciro Duarte de Carvalho; Cristiano de Carvalho Lana (Journal of South American Earth Sciences, 2025)

Demographic dynamics of a tropical montane rainforest: resilience to drought and implications for biodiversity conservation - Victor Braga Rodrigues Duarte; Henrique Machado Dias; Jéssica Tetzner de Oliveira; Vítor de Souza Abreu; Sustanis Horn Kunz; Gabriel Soares Lopes Gomes; Robert Gomes; Eduardo Alves Araújo; Marcos Vinicius Winckler Caldeira (Journal of Environmental Management, 2025)

Variability and General Trends in the Geographic Distribution and Climatic Niche of Endemic and Cosmopolitan Drosophilidae Species in Subtropical Regions of the Neotropics - Letícia Souto Freitas; Lucas Baptista Duarte; Stela Machado; Marco Silva Gottschalk; Lizandra Jaqueline Robe (Neotropical Entomology, 2025)

New records on autogenic behavior among populations of Ornithodoros fonsecai (Labruna and Venzal, 2009) (Ixodida: Argasidae) from northeastern Brazil - Ana Carolina Castro-Santiago; Leidiane Lima-Duarte; Jaqueline Valeria Camargo; Simone Michaela Simons; Ricardo Bassini-Silva; Ana Cláudia Calchi; Glauber Meneses Barboza de Oliveira; Maurício Cláudio Horta; Sebastián Muñoz-Leal; Marcelo Bahia Labruna; Marcos Rogério André; Rosangela Zacarias Machado; et al. (Veterinary Research Communications, 2025)

Effect of density and size of inert particles in an alternative rotary dryer applied to paste-like material - Isabela P. Menezes; Claudio R. Duarte; Marcos A.S. Barrozo (Food and Bioproducts Processing, 2025)

Machine learning assessment of dredging impacts on the phytoplankton community on the Brazilian equatorial margin: A multivariate analysis - Marco Valério Jansen Cutrim; Ana Karoline Duarte dos Santos Sá; Quedyane Silva da Cruz; Andrea Christina Gomes de Azevedo-Cutrim; Ricardo Luvizotto Santos; Francisco José da Silva Dias; Marianna Basso Jorge; Lisana Furtado Cavalcanti-Lima (Environmental Pollution, 2025)

Fast, in situ, and eco-friendly determination of Mn in plant leaves using portable X-ray fluorescence spectrometry for agricultural and environmental applications - Marcela Vieira da Costa; Guilherme Lopes; Luiz Roberto Guimarães Guilherme; Fábio Aurélio Dias Martins; Kellen Nara Silva; Leônidas Canuto dos Santos; Marco Aurélio Carbone Carneiro; Mariene Helena Duarte; Bruno Teixeira Ribeiro (Environmental Monitoring and Assessment, 2025)

Molecular responses in the intestine of Atlantic salmon (Salmo salar) following light and diet stimulation of smoltification: Potential molecular markers for a seawater-ready smolt - Pasqualina Gaetano; Vilma Duarte; Anja Striberny; David G. Hazlerigg; Even H. Jørgensen; Marco A. Campinho; Juan Fuentes (Aquaculture, 2025)

Cryogenian magmatic arc detrital ages and superposition of metamorphic events in metasedimentary rocks from the Andrelândia and Juiz de Fora domains, Juiz de Fora, Minas Gerais - André Campos Rocha; Beatriz Paschoal Duarte; Mauro Cesar Geraldes; Ariane Felix Coelho Azevedo; Thayla Almeida Teixeira Vieira; Rafael Cardoso de Moraes Telles; Marcos Silva Machado; Wagner Travassos Lemos; Julio Cezar Mendes (Journal of South American Earth Sciences, 2025)

Morphometry of a partial Late Pleistocene dhole (Cuon alpinus europaeus (Bourguignat, 1868); Carnivora, Canidae) skeleton from Llonin Cave (Asturias, Spain) and its taphonomic origin - Alfred Sanchis; Elsa Duarte; Leopoldo Pérez; Cristina Real; Asier Gómez-Olivencia; Francisco Pastor; Marco de la Rasilla (Geobios, 2025)

First report of Colletotrichum musicola causing anthracnose on Dioscorea alata - Ana Gabriele Gurgel Amaral; Ingrid Gomes Duarte; Anthony Carlos da Silva; Fernanda Oliveira da Silva; Willie Anderson dos Santos Vieira; Stephan Miller; Lisa A. Castlebury; Marcos Paz Saraiva Camara (Journal of Plant Pathology, 2025)

Peptide-based immunoprotection against Rhipicephalus microplus tick - Renato Andreotti; Marcos Valério Garcia; Jacqueline Cavalcante Barros; Leandra Marla Oshiro; Namor Pinheiro Zimmermann; Leandro de Oliveira Souza Higa; Pâmella Oliveira Duarte; Rodrigo Casquero Cunha (Veterinary Parasitology, 2024)

Taxonomic, Functional and Phylogenetic Beta Diversity of Upland Forest Birds in the Amazon: The Relative Importance of Biogeographic Regions, Climate and Geographic Distance - Sara Miranda Almeida; Cristian Dambros; Leandro da Silva Duarte; Pablo Cerqueira; Leandro Juen; Marcos Pérsio Dantas Santos (Journal of Biogeography, 2024)
Aim We address the relative importance of biogeographic regions (areas of endemism), regional climate and spatial factors on taxonomic, functional and phylogenetic beta diversity of bird assemblages in upland terra‐firme forests in the Amazon. Location Amazon biome. Taxon Birds. Methods We gathered 27,498 occurrence records of 873 bird species for 115 bird assemblages distributed in all nine biogeographic regions delimited by the major Amazonian rivers. Only data from studies surveying whole communities with standard sampling methods and exhaustive sampling effort were included. We partitioned the fractions of taxonomic, functional and phylogenetic beta diversity explained by climate, biogeographic regions, spatial factors and the variation shared between them. Results Across the entire Amazon, we found higher total taxonomic (0.68 ± 0.10) than phylogenetic (0.46 ± 0.08) β‐diversity, and low functional β‐diversity (0.34 ± 0.08). Biogeographic regions showed the highest unique contributions explaining taxonomic and phylogenetic β‐total (7% and 5%, respectively) and turnover components (7% of β‐jtu taxonomic, 7% of β‐jtu phylogenetic), but accounted for only 2% of total functional β‐diversity and trait turnover. Climatic variables explained slightly more trait nestedness (5%) compared with species and lineage turnover (3% each). Species composition was clearly distinct between biogeographical regions limited by the Amazon River, but support for the effect of other rivers was mixed. Main Conclusions Our study highlights the significant influence of biogeographic regions and climate on species composition in the Amazon. However, our findings also suggest that the Amazon River exerts a more pronounced impact on species distribution compared with other major Amazonian rivers. Species turnover across biogeographical regions is particularly evident at the species level, with minor effects observed in functional traits, suggesting that taxonomic turnover is driven mainly by functionally redundant species. In addition, recent diversification events, occurring predominantly at the tips of the phylogeny without substantial turnover at deeper nodes, are likely responsible for the patchy distribution of species across Amazonia.

Disentangling the veil line for Brazilian biodiversity: An overview from two long-term research programs reveals huge gaps in ecological data reporting - Aretha Franklin Guimaraes; Luciano Carramaschi de Alagao Querido; Taina Rocha; Domingos de Jesus Rodrigues; Pedro Lage Viana; Helena de Godoy Bergallo; Geraldo Wilson Fernandes; Tiago Shizen Pacheco Toma; Helena Streit; Gerhard Ernst Overbeck; Alberico Queiroz Salgueiro de Souza; Albertina Pimentel Lima; et al. (Science of The Total Environment, 2024)

Optimizing sheep growth curves using a meta-heuristic algorithm - Marco Antonio Campos Benvenga; Irenilza de Alencar Nääs; Nilsa Duarte da Silva Lima; Aylpy Renan Dutra Santos; Fernando Miranda de Vargas Junior (Tropical Animal Health and Production, 2024)

Assessing the of carbon and nitrogen storage potential in Khaya spp. stands in Southeastern Brazil - Gabriel Soares Lopes Gomes; Marcos Vinicius Winckler Caldeira; Robert Gomes; Victor Braga Rodrigues Duarte; Dione Richer Momolli; Tiago de Oliveira Godinho; Sarah Ola Moreira; Paulo André Trazzi; Laio Silva Sobrinho; Angélica de Cássia Oliveira Carneiro; Mauro Valdir Schumacher (New Forests, 2024)

Biorational products in the management of leaf spot and grape ripe rot in Vitis labrusca - André Luiz Graf; Camilla Castellar; Marcos Paulo Rosa; Renan Reisdorfer Schorr; Francisco de Assis Marques; Miguel Daniel Noseda; Henrique da Silva Silveira Duarte; Louise Larissa May De Mio (Australasian Plant Pathology, 2024)

Cytauxzoon brasiliensis sp. nov. (Apicomplexa: Theileriidae), a new species infecting a little-spotted-cat (Leopardus tigrinus) (Carnivora: Felidae) from Brazil - Matheus Almeida Duarte; Camila Manoel de Oliveira; Sandy Menezes Honorato; Liliane Maria do Rosario Batista; Janaína Tavares Mendonça; Davi Emanuel Ribeiro de Sousa; Liria Queiroz Luz Hirano; Marcos Rogério André; Márcio Botelho de Castro; Giane Regina Paludo (Systematic Parasitology, 2024)

Spatial heterogeneity of zooplankton community in an eutrophicated tropical estuary - Rayane Serra Rosas; Andrea Christina Gomes Azevedo-Cutrim; Marco Valério Jansen Cutrim; Quedyane Silva da Cruz; Danielle Stephane Campos Souza; Ana Karoline Duarte dos Santos Sá; Ana Virginia Gomes Oliveira; Taíza Pimentel Santos (Aquatic Sciences, 2024)

Improving the quality of Arabica coffee (Coffea arabica L.) through innovative optimization of roto-aerated drying - Paulo Sérgio de Andrade; Claudio Roberto Duarte; Marcos Antonio de Souza Barrozo (Innovative Food Science & Emerging Technologies, 2024)

Reproductive ecology of treefrogs: egg size promotes reproductive effort differences between females - Marcos Nathan Horato; Marlon Almeida-Santos; Carlos Frederico Duarte Rocha; Leandro Talione Sabagh (Evolutionary Ecology, 2024)

Effects of two external cooling strategies on physiological and perceptual responses of athletes with tetraplegia during and after exercise in the heat - Ingrid Ludimila Bastos Lôbo; Samuel Penna Wanner; Renato de Carvalho Guerreiro; Bruno Lourenço Pinto Coelho; Felipe Emanuel dos Santos Coimbra; Maria Eduarda Machado Martins; Larissa Cristina de Abreu Duarte; Eduardo Stieler; Marco Túlio de Mello; Andressa Silva (Journal of Thermal Biology, 2024)

Oxygen supersaturation adds resistance to a cnidarian: Symbiodiniaceae holobiont under moderate warming in experimental settings - Silvia Arossa; Shannon G. Klein; Elisa Garuglieri; Alexandra Steckbauer; Anieka J. Parry; Jacqueline V. Alva Garcia; Taiba Alamoudi; Xinyuan Yang; Shiou-Han Hung; Octavio R. Salazar; Ramona Marasco; Marco Fusi; et al. (Frontiers in Marine Science, 2024)
Ocean warming reduces O 2 solubility and increases organismal O 2 demand, endangering marine life. Coastal ecosystems, however, experience O 2 supersaturation during peak daytime temperatures due to metabolic cycles. Recent discoveries show that this environmental supersaturation can reduce the vulnerability of tropical species to warming by satisfying their oxygen requirements. To test whether this also occurs within the cnidarian holobiont, we elevated internal O 2 in Cassiopea andromeda at nighttime (i.e. holobiont respiration prevails on Symbiodniaceae O 2 production) relying on bell pulsation for ventilation, then experimentally subjected them to thermal stress (+1°C day -1 ). Though ecologically unrealistic, this approach verified our hypothesis and eliminated confounding factors. Holobionts were exposed to either constant levels of 100% air saturation (100AS) or nighttime supersaturation (NSS; where 100% air saturation transitioned to O 2 supersaturation at nighttime). At sublethal temperatures, supersaturation mitigated reductions in holobiont size of ~ 10.37% (-33.418% ± 0.345 under 100AS vs -23.039% ± 0.687 under NSS). Supersaturation alleviated chlorophyll- a loss by 42.73% until 34°C, when counteraction of this process could not be sustained due to excessive thermal stress. Supersaturation also enriched potentially beneficial bacterial taxa of the microbiome and selected a more consistent bacterial community. Although modest, the detected effects show that a O 2 surplus increased the resistance of the holobionts to thermal stress.

Protection of cowpea seeds and toxicity against cowpea weevils by the essential oils from Lippia alba (verbenaceae) and Schinus terebinthifolius (anacardiaceae) - Rafael Torre; Elisabeth Alves Duarte Pereira de Medeiros; Camila da Silva Barbosa Pereira; Ana Clara Ramos Menezes; Igor Sampaio Fontes; Larissa Vitória Ribeiro Pereira; Diego Henrique Fernandes Paiva; André Marques dos Santos; Pedro Corrêa Damasceno Junior; Marco Andre Alves de Souza (Crop Protection, 2024)

Lactobacillus delbrueckii CIDCA 133 fermented milk modulates inflammation and gut microbiota to alleviate acute colitis - Luís Cláudio Lima de Jesus; Andria dos Santos Freitas; Joyce da Cruz Ferraz Dutra; Gabriela Munis Campos; Monique Ferrary Américo; Juliana Guimarães Laguna; Evandro Gonçalves Dornelas; Rodrigo Dias de Oliveira Carvalho; Kátia Duarte Vital; Simone Odília Antunes Fernandes; Valbert Nascimento Cardoso; Jamil Silvano de Oliveira; et al. (Food Research International, 2024)

ENSO effects on the relationship between aerosols and evapotranspiration in the south of the Amazon biome - Rafael Palácios; Daniela Castagna; Luzinete Barbosa; Adilson P. Souza; Breno Imbiriba; Cornélio A. Zolin; Danielle Nassarden; Leilane Duarte; Fernando G. Morais; Marco A. Franco; Glauber Cirino; Paulo Kuhn; et al. (Environmental Research, 2024)

Evaluating the bioactivity and toxicity of Siparuna guianensis Aublet (Siparunaceae) leaf extracts in zebrafish - Maria de Fátima Santos; William Franco Carneiro; Bárbara do Carmo Rodrigues Virote; Kiara Cândido Duarte da Silva; Tassia Flavia Dias Castro; Aline Pereira Coli; Luis David Solis Murgas; Marcos Ferrante; Manuel Losada Gavilanes; Elisangela Elena Nunes Carvalho (Advances in Traditional Medicine, 2024)

Assessing the euryhaline characteristics and metabolic responses of meagre (Argyrosomus regius) when reared under different salinities: Opportunities for aquaculture refinement - Marco F.L. Lemos; Cátia S.E. Silva; Lénia D. Rato; Alexandre F.S. Marques; Ricardo Passos; Irina A. Duarte; Bernardo Duarte; Vanessa F. Fonseca; Sara C. Novais (Aquaculture, 2024)

Endophytic species of Colletotrichum associated with cashew tree in northeastern Brazil - Diana Gissell Barreto Ramos; Ana Gabriele Gurgel Amaral; Ingrid Gomes Duarte; Anthony Carlos da Silva; Willie Anderson dos Santos Vieira; Lisa A. Castlebury; Marcos Paz Saraiva Câmara (Fungal Biology, 2024)

Camera trap surveys of A tlantic F orest mammals: A data set for analyses considering imperfect detection (2004–2020) - Ingridi Camboim Franceschi; Rubem Augusto da Paixão Dornas; Isabel Salgueiro Lermen; Artur Vicente Pfeifer Coelho; Ademir Henrique Vilas Boas; Adriano Garcia Chiarello; Adriano Pereira Paglia; Agnis Cristiane de Souza; Alana Rafaela Borsekowsky; Alessandro Rocha; Alex Bager; Alexander Zaidan de Souza; et al. (Ecology, 2024)
Camera traps became the main observational method of a myriad of species over large areas. Data sets from camera traps can be used to describe the patterns and monitor the occupancy, abundance, and richness of wildlife, essential information for conservation in times of rapid climate and land‐cover changes. Habitat loss and poaching are responsible for historical population losses of mammals in the Atlantic Forest biodiversity hotspot, especially for medium to large‐sized species. Here we present a data set from camera trap surveys of medium to large‐sized native mammals (>1 kg) across the Atlantic Forest. We compiled data from 5380 ground‐level camera trap deployments in 3046 locations, from 2004 to 2020, resulting in 43,068 records of 58 species. These data add to existing data sets of mammals in the Atlantic Forest by including dates of camera operation needed for analyses dealing with imperfect detection. We also included, when available, information on important predictors of detection, namely the camera brand and model, use of bait, and obstruction of camera viewshed that can be measured from example pictures at each camera location. Besides its application in studies on the patterns and mechanisms behind occupancy, relative abundance, richness, and detection, the data set presented here can be used to study species' daily activity patterns, activity levels, and spatiotemporal interactions between species. Moreover, data can be used combined with other data sources in the multiple and expanding uses of integrated population modeling. An R script is available to view summaries of the data set. We expect that this data set will be used to advance the knowledge of mammal assemblages and to inform evidence‐based solutions for the conservation of the Atlantic Forest. The data are not copyright restricted; please cite this paper when using the data.

Adaptive response of prokaryotic communities to extreme pollution flooding in a Paleolithic rock art cave (Pindal Cave, northern Spain) - Tamara Martin-Pozas; Soledad Cuezva; Angel Fernandez-Cortes; Maria Gonzalez-Pumariega; Javier Elez; Elsa Duarte; Marco de la Rasilla; Juan Carlos Canaveras; Cesareo Saiz-Jimenez; Sergio Sanchez-Moral (Science of The Total Environment, 2024)

The impact of methylene blue photosensitizer, aPDT and a calcium hydroxide-based paste on the physicochemical and mechanical characteristics of root canal dentin and the bonding interface of fiberglass posts - Henrico Badaoui Strazzi-Sahyon; Henrique Augusto Banci; Thalya Fernanda Horsth Maltarollo; Carolina Martins Teixeira Martinez; Eloísa Alexo Rocha; Roberto Braga Figueiredo; Dayana Cristina Silva Garcia; Carlos José Leopoldo Constantino; Rubens Spin-Neto; Marco Antonio Hungaro Duarte; Luciano Tavares Angelo Cintra; Paulo Henrique dos Santos; et al. (Journal of Photochemistry and Photobiology B: Biology, 2024)

Nutritional parameters and productive performance of grazing sheep using castor bean cake as supplement or fertilizer - Abner José Girão Meneses; Roberto Cláudio Fernandes Franco Pompeu; Hévila Oliveira Salles; Clésio dos Santos Costa; Marcos Cláudio Pinheiro Rogério; Igo Renan Albuquerque de Andrade; Rafael Nogueira Furtado; Ariosvaldo Nunes de Medeiros; Patrício Leandro Pereira; Magno José Duarte Cândido (Tropical Animal Health and Production, 2024)

A demographic model to forecast Dinophysis acuminata harmful algal blooms - Vasco Manuel Nobre de Carvalho da Silva Vieira; Teresa Leal Rosa; Luís Sobrinho-Gonçalves; Marcos Duarte Mateus; Bernardo Mota (Frontiers in Marine Science, 2024)
Harmful algal blooms (HABs) in marine environments have significant adverse effects on public health, aquaculture and recreational activities. Surges of certain phytoplanktonic toxin-producing microalgae (mostly dinoflagellates or diatoms species) can induce Amnesic, Diarrhetic or Paralytic Shellfish Poisoning (ASP, DSP and PSP). Among HAB species, the genus Dinophysis leads to DSP in human consumers; this being the most recurrent problem in the Iberian Peninsula with the biggest economic impact on clam production and harvesting. While complete elimination of HABs is not feasible, timely implementation of appropriate measures can prevent their negative consequences. This is critical for aquaculture. Research on D. acuminata (dominant Dinophysis species in the North Atlantic) has been focused on ecophysiology and population dynamics, although with few modelling attempts. Weekly monitoring along the Portuguese coast since 2006 has revealed that D. acuminata thrives under spring/summer photosynthetically active radiation (PAR) coupled with water temperatures below 20°C, which typically coincide with the local upwelling regime. In order to advance this knowledge numerically, we developed a demographic model linking D. acuminata growth rate to PAR and sea surface temperature (SST). The 13-year (1-Jan-2006 to 31-Dec-2018) time-series of observations was closely fit by model forecasts. However, the model demonstrated limitations in issuing timely warnings of harmful proliferation of D. acuminata, failing to do so in 50% of cases, and issuing incorrect warnings in 5% of the cases. Furthermore, improving the odds of emitting timely warnings always worsened the odds of emitting false warnings, and vice-versa. To simultaneously improve both aspects, the modelling results clearly indicated the need of implementing both census/projection intervals smaller than 7 days and a laboratory detection limit below 20 cell/L. The time resolution of the census and of the model proved to be the most limiting factor that must be addressed in order to improve numerical forecasting of HABs.

Heterogeneous Photocatalysis for Efficient Degradation of Lamivudine and Zidovudine Antiretroviral Drugs: Assessment Toxicological in Carrot and Tomato Seeds - Alex Leandro Andrade de Lucena; Marta Maria Menezes Bezerra Duarte; Joan Manuel Rodriguez-Diaz; Rayany Magali da Rocha Santana; Émerson Felipe Mendonça da Silva; Marcos André Soares de Oliveira; Luciano Costa Almeida; Daniella Carla Napoleão (Water, Air, & Soil Pollution, 2024)

A Novel Digital Educational Strategy Improves Treatment Adherence and Quality of Life in Patients with Multiple Myeloma - Juan Guio; Andrés Melo; Mateo Mejía Saldarriaga; Cynthia Fuentes; Natalia Tíjaro-Ovalle; Andrés Borda; Yuli Guzmán; Elías Bolaños; Guillermo Quintero; Mónica Duarte; Claudia Agudelo; Soraya Aparicio; et al. (Journal of Cancer Education, 2024)

“Effects of soil management, rotation and sequence of crops on soil nitrous oxide emissions in the Cerrado: A multi-factor assessment” - Alexsandra Duarte de Oliveira; Fabiana Piontekowski Ribeiro; Cícero Célio de Figueiredo; Artur Gustavo Muller; Juaci Vitoria Malaquias; Isis Lima dos Santos; Marcos Aurélio Carolino de Sá; João Paulo Guimarães Soares; Marcos Vinícius Araújo dos Santos; Arminda Moreira de Carvalho (Journal of Environmental Management, 2023)

Kinetic study of glycerol hydrodeoxygenation on Al2O3 and NiMo2C/Al2O3 catalysts - Rafael Belo Duarte; Marcos Lúcio Corazza; João Lourenço Castagnari Willimann Pimenta; Luiz Mario de Matos Jorge (Fuel, 2023)

Green roofs are effective in cooling and mitigating urban heat islands to improve human thermal comfort - Taize Calvacante Santana; Cristiane Guiselini; Abelardo Antônio de Assunção Montenegro; Héliton Pandorfi; Rodes Angelo Batista da Silva; Renan da Silva e Silva; Pedro Henrique Dias Batista; Sávio Duarte Lopes Cavalcanti; Nicoly Farias Gomes; Marcos Vinícius da Silva; Alexandre Maniçoba da Rosa Ferraz Jardim (Modeling Earth Systems and Environment, 2023)

Cactus–sorghum intercropping combined with management interventions of planting density, row orientation and nitrogen fertilisation can optimise water use in dry regions - Thieres George Freire da Silva; Rômulo Sátiro de Medeiros; Francisco Dirceu Duarte Arraes; Clóvis Manoel Carvalho Ramos; George do Nascimento Araújo Júnior; Alexandre Maniçoba da Rosa Ferraz Jardim; Cleber Pereira Alves; Fleming Sena Campos; Marcos Vinícius da Silva; José Edson Florentino de Morais; Carlos André Alves de Souza; Sérvulo Mercier Siqueira e Silva; et al. (Science of The Total Environment, 2023)

Akanthomyces diversity in Brazil and their pathogenicity to plant-sucking insects - Rogerio Biaggioni Lopes; Tamires Aparecida Duarte Souza; Gabriel Moura Mascarin; Daniela Aguiar Souza; Wagner Bettiol; Hebert Ribeiro Souza; Marcos Faria (Journal of Invertebrate Pathology, 2023)

Biochar and Forage Peanut improve pastures: Evidence from a field experiment in Brazil - Agnieszka E. Latawiec; Aline F. Rodrigues; Katarzyna A. Korys; Maiara Mendes; Marcio Rangel; Ana Castro; Wenceslau Teixeira; Judson F. Valentim; Ednaldo Araujo; Luiz Fernando Duarte de Moraes; Vinicius Pacheco; Marcos Mendes; et al. (Agriculture, Ecosystems & Environment, 2023)

Screening of medicinal plants from El Salvador for anti-viral activity against Herpes simplex 1 - José Franco-Espínola; Marvin J. Núñez; Y. Mabel Sanabria-Ramírez; Carlos Fabio Villar-Duarte; Ulises G. Castillo; Guadalupe Cantero-González; Marcos Florentín-Pavía; Patricia Langjahr; Pablo Hernán Sotelo Torres (Natural Product Research, 2023)

Variability in leaf traits reveals contrasting strategies between forest and grassland woody communities across southern Brazil - Joice Klipel; Sandra Cristina Müller; Mariana Gliesch; Leandro Duarte; Marcos Bergmann Carlucci; Rodrigo Scarton Bergamin (Flora, 2023)

Cover plants can contribute on macronutrient accumulation in agroforestry systems during off-season - Everton Martins Arruda; Leonardo Santos Collier; Kevein Ruas Oliveira; Rilner Alves Flores; Leonardo Rodrigues Barros; Risely Ferraz-Almeida; Bruna Bandeira Nascimento; Marcos Paulo Santos; Tiago Camilo Duarte; Carlos Augusto Oliveira Andrade (Agroforestry Systems, 2023)

High accumulation of lipofuscin is observed in preantral follicles of adult goat ovaries: Is it a senescence sign? - Marília Lima; Naíza Arcângela Ribeiro de Sá; Marco Aurélio Schiavo Novaes; Gaby Judith Quispe Palomino; Gildas Mbemya Tetaping; César Carneiro Linhares Fernandes; Drielle Neske Garcia; Davide Rondina; Augusto Schneider; José Ricardo Figueiredo; Ana Beatriz Graça Duarte; Ana Paula Ribeiro Rodrigues (Small Ruminant Research, 2023)

Prepubertal to adulthood exposure to low doses of glyphosate-based herbicide increases the expression of the Havcr1 (Kim1) biomarker and causes mild kidney alterations - Claudia Paloma Gadotti; Jeane Maria Oliveira; Joyce Maria de Oliveira Bender; Marina Duartes Fernandes de Souza Lima; Guilherme Ribas Taques; Sueli Pércio Quináia; Marco Aurelio Romano; Renata Marino Romano (Toxicology and Applied Pharmacology, 2023)

Environmental heterogeneity of a tropical river-to-sea continuum and its relationship with structure and phytoplankton dynamics – Lençóis Maranhenses National Park - Quedyane Silva da Cruz; Marco Valério Jansen Cutrim; Taiza Pimentel Santos; Ana Karoline Duarte dos Santos Sá; Lisana Furtado Cavalcanti-Lima (Marine Environmental Research, 2023)

Photoperiod and dietary treatment in freshwater modulate the short-term intestinal response to seawater in Atlantic salmon (Salmo salar) - Pasqualina Gaetano; Vilma Duarte; Anja Striberny; David Hazlerigg; Even H. Jørgensen; Marco A. Campinho; Juan Fuentes (Aquaculture, 2023)

Modulation of intestinal growth and differentiation by photoperiod and dietary treatment during smoltification in Atlantic salmon (Salmo salar, L.) - Vilma Duarte; Pasqualina Gaetano; Anja Striberny; David Hazlerigg; Even H. Jørgensen; Juan Fuentes; Marco A. Campinho (Aquaculture, 2023)

Numerical analysis of the flow field and cross section design implications in a multifunctional artificial reef - Dmytro Maslov; Eduardo Pereira; Duarte Duarte; Tiago Miranda; Vasco Ferreira; Marcos Tieppo; Fábio Cruz; Jessica Johnson (Ocean Engineering, 2023)

Atlantic flower–invertebrate interactions: A data set of occurrence and frequency of floral visits - Danilo Boscolo; Bárbara Nobrega Rodrigues; Patrícia Alves Ferreira; Luciano Elsinor Lopes; Vinicius Rodrigues Tonetti; Isabela Cristhina Reis dos Santos; Juliana Akemi Hiruma‐Lima; Laura Nery; Karoline Baptista de Lima; Jéssica Perozi; André Victor Lucci Freitas; Blandina Felipe Viana; et al. (Ecology, 2023)
Encounters between flowers and invertebrates are key events for the functioning of tropical forests. Assessing the structure of networks composed of the interactions between those partners leads to a better understanding of ecosystem functioning and the effects of environmental factors on ecological processes. Gathering such data is, however, costly and time‐consuming, especially in the highly diverse tropics. We aimed to provide a comprehensive repository of available flower–invertebrate interaction information for the Atlantic Forest, a South American tropical forest domain. Data were obtained from published works and “gray literature,” such as theses and dissertations, as well as self‐reports by co‐authors. The data set has ~18,000 interaction records forming 482 networks, each containing between one and 1061 interaction links. Each network was sampled for about 200 h or less, with few exceptions. A total of 641 plant genera within 136 different families and 39 orders were reported, with the most abundant and rich families being Asteraceae, Fabaceae, and Rubiaceae. Invertebrates interacting with these plants were all arthropods from 10 orders, 129 families, and 581 genera, comprising 2419 morphotypes (including 988 named species). Hymenoptera was the most abundant and diverse order, with at least six times more records than the second‐ranked order (Lepidoptera). The complete data set shows Hymenoptera interacting with all plant orders and also shows Diptera, Lepidoptera, Coleoptera, and Hemiptera to be important nodes. Among plants, Asterales and Fabales had the highest number of interactions. The best sampled environment was forest (~8000 records), followed by pastures and crops. Savanna, grasslands, and urban environments (among others) were also reported, indicating a wide range of approaches dedicated to collecting flower–invertebrate interaction data in the Atlantic Forest domain. Nevertheless, most reported data were from forest understory or lower strata, indicating a knowledge gap about flower–invertebrate interactions at the canopy. Also, access to remote regions remains a limitation, generating sampling bias across the geographical range of the Atlantic Forest. Future studies in these continuous and hard‐to‐access forested areas will yield important new information regarding the interactions between flowers and invertebrates in the Atlantic Forest. There are no copyright restrictions on the data set. Please cite this data paper if the data are used in publications and teaching events.

Macrozoobenthos monitoring in Portuguese transitional waters in the scope of the water framework directive using morphology and DNA metabarcoding - Sofia Duarte; Pedro E. Vieira; Barbara R. Leite; Marcos A.L. Teixeira; João M. Neto; Filipe O. Costa (Estuarine, Coastal and Shelf Science, 2023)

Colletotrichum karsti causing anthracnose on Dioscorea cayennensis in Brazil - Ana Gabriele Gurgel Amaral; Ingrid Gomes Duarte; Willie Anderson dos Santos Vieira; Ailton Reis; Lisa A. Castlebury; Marcos P. S. Câmara (Journal of Plant Pathology, 2023)

Morphological characteristics and yield of Opuntia stricta and Nopalea cochenillifera in integrated crop systems with caatinga trees - Clemente Fernandes dos Santos Neto; Rodrigo Gregório da Silva; Samuel Rocha Maranhão; Cleber Medeiros Barreto; Marcos Neves Lopes; Magno José Duarte Cândido (Agroforestry Systems, 2023)

Biological pilot treatment reduces physicochemical and microbiological parameters of dairy cattle wastewater - Marcos Filgueiras Jorge; Leonardo Duarte Batista da Silva; Jonathas Batista Gonçalves Silva; Dinara Grasiela Alves; Cristina Moll Huther; Daiane Cecchin; José Guilherme Marinho Guerra; Luise Maria Martins dos Santos; João Paulo Francisco; Antonio Carlos Farias de Melo; Alexandre Lioi Nascentes; Rozileni Piont Kovsky Caletti (Environmental Science and Pollution Research, 2022)

Castor bean cake for the control of parasites in pasture-finished sheep - Abner José Girão Meneses; Roberto Cláudio Fernandes Franco Pompeu; Hévila Oliveira Salles; Luiz da Silva Vieira; Marcel Teixeira; Marcos Cláudio Pinheiro Rogério; Ana Márjory Paiva Sousa; Patrício Leandro Pereira; Magno José Duarte Cândido (Tropical Animal Health and Production, 2022)

Acidification and high-temperature impacts on energetics and shell production of the edible clam Ameghinomya antiqua - Sebastián I. Martel; Carolina Fernández; Nelson A. Lagos; Fabio A. Labra; Cristián Duarte; Juan F. Vivanco; Claudio García-Herrera; Marco A. Lardies (Frontiers in Marine Science, 2022)
Warming and ocean acidification are currently critical global change drivers for marine ecosystems due to their complex and irreversible effects on the ecology and evolution of marine communities. Changes in the chemistry and the temperature of the ocean impact the biological performance of marine resources by affecting their energy budget and thus imposing energetic restrictions and trade-offs on their survival, growth, and reproduction. In this study, we evaluated the interplaying effects of increased p CO 2 levels and temperature on the economically relevant clam Ameghinomya antiqua , an infaunal bivalve inhabiting a wide distributional range along the coast of Chile. Juvenile clams collected from southern Chile were exposed to a 90-day experimental set-up emulating the current and a future scenario projeced to the end of the current century for both high p CO 2 /low-pH and temperature (10 and 15°C) projected for the Chilean coast. Clams showed physiological plasticity to different projected environmental scenarios without mortality. In addition, our results showed that the specimens under low-pH conditions were not able to meet the energetic requirements when increased temperature imposed high maintenance costs, consequently showing metabolic depression. Indeed, although the calcification rate was negative in the high- p CO 2 scenario, it was the temperature that determined the amount of shell loss. These results indicate that the studied clam can face environmental changes for short-term periods modifying energetic allocation on maintenance and growth processes, but with possible long-term population costs, endangering the sustainability of an important benthic artisanal fisheries resource.

MicroRNAs expression profiles in early responses to different levels of water deficit in Setaria viridis - Karoline Estefani Duarte; Marcos Fernando Basso; Nelson Geraldo de Oliveira; José Cleydson Ferreira da Silva; Bruno de Oliveira Garcia; Bárbara Andrade Dias Brito Cunha; Thiago Bergamo Cardoso; Alexandre Lima Nepomuceno; Adilson Kenji Kobayashi; Thaís Ribeiro Santiago; Wagner Rodrigo de Souza; Hugo Bruno Correa Molinari (Physiology and Molecular Biology of Plants, 2022)

Agrobacterium-mediated transformation of annatto (Bixa orellana L.): protocol optimization and overexpression of microRNA 156 in transgenic plants - Daniele Vidal Faria; Débora Márcia Silva Freitas; Marcos Bruno Silva Duarte; Kleiton Lima Godoy Machado; Elyabe Monteiro Matos; Diego Silva Batista; Marcio Gilberto Cardoso Costa; Lyderson Facio Viccini; Fábio Tebaldi Silveira Nogueira; Wagner Campos Otoni (Plant Cell, Tissue and Organ Culture (PCTOC), 2022)

The water, climate and energy nexus in the São Francisco River Basin, Brazil: an analysis of decadal climate variability - José Micael Ferreira da Costa; Cleiton S. Silveira; Francisco das Chagas Vasconcelos Júnior; Antonio Duarte Marcos Junior; Marx Vinicius Maciel da Silva; Sérgio Filipe Carvalho Ramos; Victor Costa Porto; Francisco de Assis Souza Filho; Eduardo S. P. R. Martins (Hydrological Sciences Journal, 2022)

Swimming behavior of the multicellular magnetotactic prokaryote ‘Candidatus Magnetoglobus multicellularis’ near solid boundaries and natural magnetic grains - Carolina N. Keim; Daniel Mendes da Silva; Roger Duarte de Melo; Daniel Acosta-Avalos; Marcos Farina; Henrique Lins de Barros (Antonie van Leeuwenhoek, 2021)

Expression of Bacillus amyloliquefaciens transglutaminase in recombinant E. coli under the control of a bicistronic plasmid system in DO-stat fed-batch bioreactor cultivations - Lovaine Silva Duarte; Carla Roberta Matte; Paulo Roberto Dall Cortivo; José Eduardo Sacconi Nunes; Laisa Quadros Barsé; Cristiano Valim Bizarro; Marco Antônio Záchia Ayub (Brazilian Journal of Microbiology, 2021)

Colletotrichum gloeosporioides sensu lato associated with anthracnose in Bauhinia forficata - Francisco Jorge Carlos de Souza Junior; Willie Anderson dos Santos Vieira; Josiene Silva Veloso; Ingrid Gomes Duarte; Ana Gabriele Gurgel Amaral; Delson Laranjeira; Valdir De Queiroz Balbino; Vinson P. Doyle; Marcos Paz Saraiva Câmara (European Journal of Plant Pathology, 2021)

Impact of Cashew (Anacardium occidentale L.) by-Product on Composition and Metabolic Activity of Human Colonic Microbiota In Vitro Indicates Prebiotic Properties - Francisca Nayara Dantas Duarte Menezes; Érika Tayse da Cruz Almeida; Arthur Rodrigo da Silva Vieira; Jailane de Souza Aquino; Marcos dos Santos Lima; Marciane Magnani; Evandro Leite de Souza (Current Microbiology, 2021)

Case report of respiratory aspergillosis and candidiasis in wild Magellanic penguins (Spheniscus magellanicus), Brazil - Ana Carolina Ewbank; Aricia Duarte-Benvenuto; Roberta Zamana-Ramblas; Pedro Enrique Navas-Suárez; Marco Aurélio Gattamorta; Priscilla Carla dos Santos-Costa; José Luiz Catão-Dias; Carlos Sacristán (Brazilian Journal of Microbiology, 2021)

Geographical Variation in Phenotypic Plasticity of Intertidal Sister Limpet’s Species Under Ocean Acidification Scenarios - Marco Antonio Lardies; Paz Caballero; Cristián Duarte; María Josefina Poupin (Frontiers in Marine Science, 2021)
Ocean Acidification (OA) can have pervasive effects in calcifying marine organisms, and a better understanding of how different populations respond at the physiological and evolutionary level could help to model the impacts of global change in marine ecosystems. Due to its natural geography and oceanographic processes, the Chilean coast provides a natural laboratory where benthic organisms are frequently exposed to diverse projected OA scenarios. The goal of this study was to assess whether a population of mollusks thriving in a more variable environment (Talcaruca) would present higher phenotypic plasticity in physiological and morphological traits in response to different p CO 2 when compared to a population of the same species from a more stable environment (Los Molles). To achieve this, two benthic limpets ( Scurria zebrina and Scurria viridula ) inhabiting these two contrasting localities were exposed to ocean acidification experimental conditions representing the current p CO 2 in the Chilean coast (500 μatm) and the levels predicted for the year 2100 in upwelling zones (1500 (μatm). Our results show that the responses to OA are species-specific, even in this related species. Interestingly, S. viridula showed better performance under OA than S. zebrina (i.e., similar sizes and carbonate content in individuals from both populations; lower effects of acidification on the growth rate combined with a reduction of metabolism at higher p CO2). Remarkably, these characteristics could explain this species’ success in overstepping the biogeographical break in the area of Talcaruca, which S. zebrina cannot achieve. Besides, the results show that the habitat factor has a strong influence on some traits. For instance, individuals from Talcaruca presented a higher growth rate plasticity index and lower shell dissolution rates in acidified conditions than those from Los Molles. These results show that limpets from the variable environment tend to display higher plasticity, buffering the physiological effects of OA compared with limpets from the more stable environment. Taken together, these findings highlight the key role of geographic variation in phenotypic plasticity to determine the vulnerability of calcifying organisms to future scenarios of OA.

Features of the upper tropospheric cyclonic vortices of Northeast Brazil in life cycle stages - Michelyne Duarte Coutinho de Morais; Manoel Alonso Gan; Marcos Cezar Yoshida (International Journal of Climatology, 2021)
The main purpose of the study is to explore in more detail the Upper Tropospheric Cyclonic Vortices (UTCVs) features over Northeast Brazil (NEB) in an attempt to improve weather forecasts. The various aspects of the life cycle features of the UTCVs over NEB are presented here, because these aspects have not been investigated in previous studies. Initially, the UTCVs were identified at 200 hPa, and then, they were identified at lower levels to analyse their vertical structure, using 6‐hr data for a 30‐year period (1984–2013) from the European Center for Medium Range Weather Forecasts' reanalysis (ERA Interim). An objective method was improved to obtain at first‐hand the trajectory and the vertical extent of the UTCVs over NEB. Some statistics results were consistent with previous studies related to relative frequency, duration and direction of movement. However, further results were obtained too. An average distance of 2,000 km for the UTCVs total travel was found. Of this average distance, 750 km was reached by UTCVs on the first day of the life cycle, leading to the presumption of a possible suppression of vortex movement that depends on a diabatic mechanism. We also found predominance of UTCVs without vertical tilt or with east tilt with increasing height. When considering life cycle stages (formation, maximum depth and dissipation), diversity was observed in intensity with stages, levels and seasons of the year, with spring exhibiting the most intense UTCVs over all seasons. Finally, our finding about interannual variability is novel. There was a tendency for the average number of UTCVs to be slightly higher during El Niño summers compared with La Niña summers.

Toxicity Going Nano: Ionic Versus Engineered Cu Nanoparticles Impacts on the Physiological Fitness of the Model Diatom Phaeodactylum tricornutum - Marco Franzitta; Eduardo Feijão; Maria Teresa Cabrita; Carla Gameiro; Ana Rita Matos; João Carlos Marques; Johannes W. Goessling; Patrick Reis-Santos; Vanessa F. Fonseca; Carlo Pretti; Isabel Caçador; Bernardo Duarte (Frontiers in Marine Science, 2020)
Increasing input of Metal Engineered Nano Particles (MeENPs) in marine ecosystems has raised concerns about their potential toxicity on phytoplankton. Given the lack of knowledge on MeENPs impact on these important primary producers, the effects of Copper Oxide (CuO) ENPs on growth, physiology, pigment profiles, fatty acid (FA) metabolism, and oxidative stress were investigated in the model diatom Pheodactylum tricornutum , to provide suitable biomarkers of CuO ENP exposure versus its ionic counterpart. Diatom growth was inhibited by CuO ENPs but not Ionic Cu, suggesting CuO ENP cytotoxicity. Pulse Modulated Amplitude (PAM) phenotyping evidenced a decrease in the electron transport energy flux, pointing to a reduction in chemical energy generation following CuO ENPs exposure, as well as an increase in the content of the non-functional Cu-substituted chlorophyll a (CuChl a ). A significant decrease in eicosapentaenoic acid (C20:5) associated with a significant rise in thylakoid membranes FAs reflected the activation of counteractive measures to photosynthetic impairment. Significant increase in the omega 6/omega 3 ratio, underline expectable negative repercussions to marine food webs. Increased thiobarbituric acid reactive substances reflected heightened oxidative stress by CuO ENP. Enhanced Glutathione Reductase and Ascorbate Peroxidase activity were also more evident for CuO ENPs than ionic Cu. Overall, observed molecular changes highlighted a battery of possible suitable biomarkers to efficiently determine the harmful effects of CuO ENPs. The results suggest that the occurrence and contamination of these new forms of metal contaminants can impose added stress to the marine diatom community, which could have significant impacts on marine ecosystems, namely through a reduction of the primary productivity, oxygen production and omega 6 production, all essential to sustain heterotrophic marine life.

NEOTROPICAL CARNIVORES: a data set on carnivore distribution in the Neotropics - Mariana Nagy‐Reis; Júlia Emi de Faria Oshima; Claudia Zukeran Kanda; Francesca Belem Lopes Palmeira; Fabiano Rodrigues de Melo; Ronaldo Gonçalves Morato; Lilian Bonjorne; Marcelo Magioli; Caroline Leuchtenberger; Fabio Rohe; Frederico Gemesio Lemos; Felipe Martello; et al. (Ecology, 2020)
Mammalian carnivores are considered a key group in maintaining ecological health and can indicate potential ecological integrity in landscapes where they occur. Carnivores also hold high conservation value and their habitat requirements can guide management and conservation plans. The order Carnivora has 84 species from 8 families in the Neotropical region: Canidae; Felidae; Mephitidae; Mustelidae; Otariidae; Phocidae; Procyonidae; and Ursidae. Herein, we include published and unpublished data on native terrestrial Neotropical carnivores (Canidae; Felidae; Mephitidae; Mustelidae; Procyonidae; and Ursidae). NEOTROPICAL CARNIVORES is a publicly available data set that includes 99,605 data entries from 35,511 unique georeferenced coordinates. Detection/non‐detection and quantitative data were obtained from 1818 to 2018 by researchers, governmental agencies, non‐governmental organizations, and private consultants. Data were collected using several methods including camera trapping, museum collections, roadkill, line transect, and opportunistic records. Literature (peer‐reviewed and grey literature) from Portuguese, Spanish and English were incorporated in this compilation. Most of the data set consists of detection data entries (n = 79,343; 79.7%) but also includes non‐detection data (n = 20,262; 20.3%). Of those, 43.3% also include count data (n = 43,151). The information available in NEOTROPICAL CARNIVORES will contribute to macroecological, ecological, and conservation questions in multiple spatio‐temporal perspectives. As carnivores play key roles in trophic interactions, a better understanding of their distribution and habitat requirements are essential to establish conservation management plans and safeguard the future ecological health of Neotropical ecosystems. Our data paper, combined with other large‐scale data sets, has great potential to clarify species distribution and related ecological processes within the Neotropics. There are no copyright restrictions and no restriction for using data from this data paper, as long as the data paper is cited as the source of the information used. We also request that users inform us of how they intend to use the data.

NEOTROPICAL ALIEN MAMMALS: a data set of occurrence and abundance of alien mammals in the Neotropics - Clarissa Alves da Rosa; Bruno R. Ribeiro; Vanesa Bejarano; Fernando Henrique Puertas; Adriana Bocchiglieri; Adriana Loeser dos Santos Barbosa; Adriano Garcia Chiarello; Adriano Pereira Paglia; Adriele Aparecida Pereira; Adryelle Francisca de Souza Moreira; Agnis Cristiane de Souza; Aiesca Pellegrin; et al. (Ecology, 2020)
Biological invasion is one of the main threats to native biodiversity. For a species to become invasive, it must be voluntarily or involuntarily introduced by humans into a nonnative habitat. Mammals were among first taxa to be introduced worldwide for game, meat, and labor, yet the number of species introduced in the Neotropics remains unknown. In this data set, we make available occurrence and abundance data on mammal species that (1) transposed a geographical barrier and (2) were voluntarily or involuntarily introduced by humans into the Neotropics. Our data set is composed of 73,738 historical and current georeferenced records on alien mammal species of which around 96% correspond to occurrence data on 77 species belonging to eight orders and 26 families. Data cover 26 continental countries in the Neotropics, ranging from Mexico and its frontier regions (southern Florida and coastal‐central Florida in the southeast United States) to Argentina, Paraguay, Chile, and Uruguay, and the 13 countries of Caribbean islands. Our data set also includes neotropical species (e.g., Callithrix sp., Myocastor coypus , Nasua nasua) considered alien in particular areas of Neotropics. The most numerous species in terms of records are from Bos sp. ( n = 37,782), Sus scrofa ( n = 6,730), and Canis familiaris ( n = 10,084); 17 species were represented by only one record (e.g., S yncerus caffer, Cervus timorensis, Cervus unicolor, Canis latrans ). Primates have the highest number of species in the data set ( n = 20 species), partly because of uncertainties regarding taxonomic identification of the genera Callithrix, which includes the species Callithrix aurita, Callithrix flaviceps, Callithrix geoffroyi, Callithrix jacchus, Callithrix kuhlii, Callithrix penicillata , and their hybrids. This unique data set will be a valuable source of information on invasion risk assessments, biodiversity redistribution and conservation‐related research. There are no copyright restrictions. Please cite this data paper when using the data in publications. We also request that researchers and teachers inform us on how they are using the data.

Correlation between Rhipicephalus microplus ticks and Anaplasma marginale infection in various cattle breeds in Brazil - Kauê Rodriguez Martins; Marcos Valério Garcia; Paulino Bonatte-Junior; Pãmella Oliveira Duarte; Leandro Oliveira Souza de Higa; Bárbara Guimarães Csordas; Jacqueline Cavalcante Barros; Renato Andreotti (Experimental and Applied Acarology, 2020)

Evaluation of natural regeneration and recovery of environmental services in a watershed in the Cerrado-Brazil - Gilsonley Lopes dos Santos; Marcos Gervasio Pereira; Rafael Coll Delgado; José Luiz Rodrigues Torres; Matheus Duarte da Silva Cravo; Antônio Carlos Barreto; Iris Cristiane Magistrali (Environment, Development and Sustainability, 2020)

Spotted fever group Rickettsia and Borrelia sp. cooccurrence in Amblyomma sculptum in the Midwest region of Brazil - Leandro de Oliveira Souza Higa; Bárbara Guimarães Csordas; Marcos Valério Garcia; Leandra Marla Oshiro; Pâmella Oliveira Duarte; Jacqueline Cavalcante Barros; Renato Andreotti (Experimental and Applied Acarology, 2020)

Early reprecipitation of sulfate salts in coal biodesulfurization processes using acidophilic chemolithotrophic bacteria - Paola Gissel Duarte Briceño; Gerardo Andrés Caicedo Pineda; Marco Antonio Márquez Godoy (World Journal of Microbiology and Biotechnology, 2020)

Seed germination, growth and chlorophyll a fluorescence in young plants of Allophylus edulis in different periods of flooding - Caroline Igansi Duarte; Emanuela Garbin Martinazzo; Marcos Antonio Bacarin; Ioni Gonçalves Colares (Acta Physiologiae Plantarum, 2020)

Transglutaminases: part I—origins, sources, and biotechnological characteristics - Lovaine Duarte; Carla Roberta Matte; Cristiano Valim Bizarro; Marco Antônio Záchia Ayub (World Journal of Microbiology and Biotechnology, 2020)

Review transglutaminases: part II—industrial applications in food, biotechnology, textiles and leather products - Lovaine Duarte; Carla Roberta Matte; Cristiano Valim Bizarro; Marco Antônio Záchia Ayub (World Journal of Microbiology and Biotechnology, 2020)

TRY plant trait database – enhanced coverage and open access - Jens Kattge; Gerhard Bönisch; Sandra Díaz; Sandra Lavorel; Iain Colin Prentice; Paul Leadley; Susanne Tautenhahn; Gijsbert D. A. Werner; Tuomas Aakala; Mehdi Abedi; Alicia T. R. Acosta; George C. Adamidis; et al. (Global Change Biology, 2020)
Plant traits—the morphological, anatomical, physiological, biochemical and phenological characteristics of plants—determine how plants respond to environmental factors, affect other trophic levels, and influence ecosystem properties and their benefits and detriments to people. Plant trait data thus represent the basis for a vast area of research spanning from evolutionary biology, community and functional ecology, to biodiversity conservation, ecosystem and landscape management, restoration, biogeography and earth system modelling. Since its foundation in 2007, the TRY database of plant traits has grown continuously. It now provides unprecedented data coverage under an open access data policy and is the main plant trait database used by the research community worldwide. Increasingly, the TRY database also supports new frontiers of trait‐based plant research, including the identification of data gaps and the subsequent mobilization or measurement of new data. To support this development, in this article we evaluate the extent of the trait data compiled in TRY and analyse emerging patterns of data coverage and representativeness. Best species coverage is achieved for categorical traits—almost complete coverage for ‘plant growth form’. However, most traits relevant for ecology and vegetation modelling are characterized by continuous intraspecific variation and trait–environmental relationships. These traits have to be measured on individual plants in their respective environment. Despite unprecedented data coverage, we observe a humbling lack of completeness and representativeness of these continuous traits in many aspects. We, therefore, conclude that reducing data gaps and biases in the TRY database remains a key challenge and requires a coordinated approach to data mobilization and trait measurements. This can only be achieved in collaboration with other initiatives.

Collaborative Database to Track Mass Mortality Events in the Mediterranean Sea - Joaquim Garrabou; Daniel Gómez-Gras; Jean-Baptiste Ledoux; Cristina Linares; Nathaniel Bensoussan; Paula López-Sendino; Hocein Bazairi; Free Espinosa; Mohamed Ramdani; Samir Grimes; Mouloud Benabdi; Jamila Ben Souissi; et al. (Frontiers in Marine Science, 2019)

Carnosic Acid Pretreatment Attenuates Mitochondrial Dysfunction in SH-SY5Y Cells in an Experimental Model of Glutamate-Induced Excitotoxicity - Marcos Roberto de Oliveira; Adriane Ribeiro Duarte; Aline Lukasievicz Chenet; Fhelipe Jolner Souza de Almeida; Claudia Marlise Balbinotti Andrade (Neurotoxicity Research, 2019)

Performance evaluation of AR5-CMIP5 models for the representation of seasonal and multi-annual variability of precipitation in Brazilian hydropower sector basins under RCP8.5 scenario - Cleiton Da Silva Silveira; Francisco Das Chagas Vasconcelos Junior; Francisco De Assis De Souza Filho; Sullyandro Oliveira Guimarães; Antonio Duarte Marcos Junior; Giullian Nicola Lima Dos Reis; Victor Costa Porto (Hydrological Sciences Journal, 2019)

NEOTROPICAL XENARTHRANS: a data set of occurrence of xenarthran species in the Neotropics - Paloma Marques Santos; Adriana Bocchiglieri; Adriano Garcia Chiarello; Adriano Pereira Paglia; Adryelle Moreira; Agnis Cristiane de Souza; Agustin Manuel Abba; Agustin Paviolo; Ailin Gatica; Akyllan Zoppi Medeiro; Alan Nilo Costa; Alberto Gonzalez Gallina; et al. (Ecology, 2019)
Xenarthrans—anteaters, sloths, and armadillos—have essential functions for ecosystem maintenance, such as insect control and nutrient cycling, playing key roles as ecosystem engineers. Because of habitat loss and fragmentation, hunting pressure, and conflicts with domestic dogs, these species have been threatened locally, regionally, or even across their full distribution ranges. The Neotropics harbor 21 species of armadillos, 10 anteaters, and 6 sloths. Our data set includes the families Chlamyphoridae (13), Dasypodidae (7), Myrmecophagidae (3), Bradypodidae (4), and Megalonychidae (2). We have no occurrence data on Dasypus pilosus (Dasypodidae). Regarding Cyclopedidae, until recently, only one species was recognized, but new genetic studies have revealed that the group is represented by seven species. In this data paper, we compiled a total of 42,528 records of 31 species, represented by occurrence and quantitative data, totaling 24,847 unique georeferenced records. The geographic range is from the southern United States, Mexico, and Caribbean countries at the northern portion of the Neotropics, to the austral distribution in Argentina, Paraguay, Chile, and Uruguay. Regarding anteaters, Myrmecophaga tridactyla has the most records ( n = 5,941), and Cyclopes sp. have the fewest ( n = 240). The armadillo species with the most data is Dasypus novemcinctus ( n = 11,588), and the fewest data are recorded for Calyptophractus retusus ( n = 33). With regard to sloth species, Bradypus variegatus has the most records ( n = 962), and Bradypus pygmaeus has the fewest ( n = 12). Our main objective with Neotropical Xenarthrans is to make occurrence and quantitative data available to facilitate more ecological research, particularly if we integrate the xenarthran data with other data sets of Neotropical Series that will become available very soon (i.e., Neotropical Carnivores, Neotropical Invasive Mammals, and Neotropical Hunters and Dogs). Therefore, studies on trophic cascades, hunting pressure, habitat loss, fragmentation effects, species invasion, and climate change effects will be possible with the Neotropical Xenarthrans data set. Please cite this data paper when using its data in publications. We also request that researchers and teachers inform us of how they are using these data.

Chitosan-iron oxide hybrid composite: mechanism of hexavalent chromium removal by central composite design and theoretical calculations - Pricila Maria Batista Chagas; Aline Aparecida Caetano; Marco Aurélio Rossi; Mateus Aquino Gonçalves; Teodorico de Castro Ramalho; Angelita Duarte Corrêa; Iara do Rosário Guimarães (Environmental Science and Pollution Research, 2019)

Genetic diversity and demography of the critically endangered Roberts’ false brook salamander (Pseudoeurycea robertsi) in Central Mexico - Armando Sunny; Luis Duarte-deJesus; Arlene Aguilera-Hernández; Fabiola Ramírez-Corona; Marco Suárez-Atilano; Ruth Percino-Daniel; Javier Manjarrez; Octavio Monroy-Vilchis; Andrea González-Fernández (Genetica, 2019)

Relationship between the environmental conditions and floristic patterns in two phytophysiognomies of the Brazilian Cerrado - Gilsonley Lopes dos Santos; Marcos Gervasio Pereira; Daniel Costa de Carvalho; Raíssa Nascimento dos Santos; Rafael Coll Delgado; José Luiz Rodrigues Torres; Matheus Duarte da Silva Cravo (Environment, Development and Sustainability, 2019)

ATLANTIC EPIPHYTES : a data set of vascular and non‐vascular epiphyte plants and lichens from the Atlantic Forest - Flavio Nunes Ramos; Sara Ribeiro Mortara; Nathalia Monalisa‐Francisco; João Pedro Costa Elias; Luiz Menini Neto; Leandro Freitas; Rodrigo Kersten; André Márcio Amorim; Fernando Bittencourt Matos; André Felippe Nunes‐Freitas; Suzana Alcantara; Marcia Helena Nagahama Alexandre; et al. (Ecology, 2019)
Epiphytes are hyper‐diverse and one of the frequently undervalued life forms in plant surveys and biodiversity inventories. Epiphytes of the Atlantic Forest, one of the most endangered ecosystems in the world, have high endemism and radiated recently in the Pliocene. We aimed to (1) compile an extensive Atlantic Forest data set on vascular, non‐vascular plants (including hemiepiphytes), and lichen epiphyte species occurrence and abundance; (2) describe the epiphyte distribution in the Atlantic Forest, in order to indicate future sampling efforts. Our work presents the first epiphyte data set with information on abundance and occurrence of epiphyte phorophyte species. All data compiled here come from three main sources provided by the authors: published sources (comprising peer‐reviewed articles, books, and theses), unpublished data, and herbarium data. We compiled a data set composed of 2,095 species, from 89,270 holo/hemiepiphyte records, in the Atlantic Forest of Brazil, Argentina, Paraguay, and Uruguay, recorded from 1824 to early 2018. Most of the records were from qualitative data (occurrence only, 88%), well distributed throughout the Atlantic Forest. For quantitative records, the most common sampling method was individual trees (71%), followed by plot sampling (19%), and transect sampling (10%). Angiosperms (81%) were the most frequently registered group, and Bromeliaceae and Orchidaceae were the families with the greatest number of records (27,272 and 21,945, respectively). Ferns and Lycophytes presented fewer records than Angiosperms, and Polypodiaceae were the most recorded family, and more concentrated in the Southern and Southeastern regions. Data on non‐vascular plants and lichens were scarce, with a few disjunct records concentrated in the Northeastern region of the Atlantic Forest. For all non‐vascular plant records, Lejeuneaceae, a family of liverworts, was the most recorded family. We hope that our effort to organize scattered epiphyte data help advance the knowledge of epiphyte ecology, as well as our understanding of macroecological and biogeographical patterns in the Atlantic Forest. No copyright restrictions are associated with the data set. Please cite this Ecology Data Paper if the data are used in publication and teaching events.

Combination Therapy with Sulfasalazine and Valproic Acid Promotes Human Glioblastoma Cell Death Through Imbalance of the Intracellular Oxidative Response - Carlos Gustavo Garcia; Suzana Assad Kahn; Luiz Henrique Medeiros Geraldo; Igor Romano; Ivan Domith; Deborah Christinne Lima e Silva; Fernando dos Santos Assunção; Marcos José Ferreira; Camila Cabral Portugal; Jorge Marcondes de Souza; Luciana Ferreira Romão; Annibal Duarte Pereira Netto; et al. (Molecular Neurobiology, 2018)

Molecular Mechanisms Underlying the Anti-depressant Effects of Resveratrol: a Review - Marcos Roberto de Oliveira; Aline Lukasievicz Chenet; Adriane Ribeiro Duarte; Giselli Scaini; João Quevedo (Molecular Neurobiology, 2018)

First Report of a New Isolate of Metarhizium rileyi from Maize Fields of Quivicán, Cuba - Sandra Pérez Álvarez; Amaury Méndez Guerrero; Bernardo Nayar Débora Duarte; Marco Antonio Magallanes Tapia; Jesús Alicia Chávez Medina; Yoannis Domínguez Rodríguez (Indian Journal of Microbiology, 2018)

ATLANTIC MAMMAL TRAITS : a data set of morphological traits of mammals in the Atlantic Forest of South America - Fernando Gonçalves; Ricardo S. Bovendorp; Gabrielle Beca; Carolina Bello; Raul Costa‐Pereira; Renata L. Muylaert; Raisa R. Rodarte; Nacho Villar; Rafael Souza; Maurício E. Graipel; Jorge J. Cherem; Deborah Faria; et al. (Ecology, 2018)
Measures of traits are the basis of functional biological diversity. Numerous works consider mean species‐level measures of traits while ignoring individual variance within species. However, there is a large amount of variation within species and it is increasingly apparent that it is important to consider trait variation not only between species, but also within species. Mammals are an interesting group for investigating trait‐based approaches because they play diverse and important ecological functions (e.g., pollination, seed dispersal, predation, grazing) that are correlated with functional traits. Here we compile a data set comprising morphological and life history information of 279 mammal species from 39,850 individuals of 388 populations ranging from −5.83 to −29.75 decimal degrees of latitude and −34.82 to −56.73 decimal degrees of longitude in the Atlantic forest of South America. We present trait information from 16,840 individuals of 181 species of non‐volant mammals (Rodentia, Didelphimorphia, Carnivora, Primates, Cingulata, Artiodactyla, Pilosa, Lagomorpha, Perissodactyla) and from 23,010 individuals of 98 species of volant mammals (Chiroptera). The traits reported include body mass, age, sex, reproductive stage, as well as the geographic coordinates of sampling for all taxa. Moreover, we gathered information on forearm length for bats and body length and tail length for rodents and marsupials. No copyright restrictions are associated with the use of this data set. Please cite this data paper when the data are used in publications. We also request that researchers and teachers inform us of how they are using the data.

Analyzing community‐weighted trait means across environmental gradients: should phylogeny stay or should it go? - Leandro D. S. Duarte; Vanderlei J. Debastiani; Marcos B. Carlucci; José Alexandre F. Diniz‐Filho (Ecology, 2018)
Functional traits mediate ecological responses of organisms to the environment, determining community structure. Community‐weighted trait means ( CWM ) are often used to characterize communities by combining information on species traits and distribution. Relating CWM variation to environmental gradients allows for evaluating species sorting across the metacommunity, either based on correlation tests or ordinary least squares ( OLS ) models. Yet, it is not clear if phylogenetic signal in both traits and species distribution affect those analyses. On one hand, phylogenetic signal might indicate niche conservatism along clade evolution, reinforcing the environmental signal in trait assembly patterns. On the other hand, it might introduce phylogenetic autocorrelation to mean trait variation among communities. Under this latter scenario, phylogenetic signal might inflate type I error in analysis relating CWM variation to environmental gradients. We explore multiple ways phylogenetic history may influence analysis relating CWM to environmental gradients. We propose the concept of neutral trait diffusion, which predicts that for a functional trait x , CWM variation among local communities does not deviate from the expectation that x evolved according to a neutral evolutionary process. Based on this framework we introduce a graphical tool called neutral trait diffusion representation ( NTDR ) that allows for the evaluation of whether it is necessary to carry out phylogenetic correction in the trait prior to analyzing the association between CWM and environmental gradients. We illustrate the NTDR approach using simulated traits, phylogenies and metacommunities. We show that even under moderate phylogenetic signal in both the trait used to define CWM and species distribution across communities, OLS models relating CWM variation to environmental gradients lead to inflated type I error when testing the null hypothesis of no association between CWM and environmental gradient. To overcome this issue, we propose a phylogenetic correction for OLS models and evaluate its statistical performance (type I error and power). Phylogeny‐corrected OLS models successfully control for type I error in analysis relating CWM variation to environmental gradients but may show decreased power. Combining the exploratory tool of NTDR and phylogenetic correction in traits, when necessary, guarantees more precise inferences about the environmental forces driving trait‐mediated species sorting across metacommunities.

Myrcia incompleta (Myrtaceae), a new species from Amazonian Brazil - Marcos Sobral; Maria Anália Duarte De Souza (Brittonia, 2017)

ATLANTIC ‐ CAMTRAPS : a dataset of medium and large terrestrial mammal communities in the Atlantic Forest of South America - Fernando Lima; Gabrielle Beca; Renata L. Muylaert; Clinton N. Jenkins; Miriam L. L. Perilli; Ana Maria O. Paschoal; Rodrigo L. Massara; Adriano P. Paglia; Adriano G. Chiarello; Maurício E. Graipel; Jorge J. Cherem; André L. Regolin; et al. (Ecology, 2017)
Our understanding of mammal ecology has always been hindered by the difficulties of observing species in closed tropical forests. Camera trapping has become a major advance for monitoring terrestrial mammals in biodiversity rich ecosystems. Here we compiled one of the largest datasets of inventories of terrestrial mammal communities for the Neotropical region based on camera trapping studies. The dataset comprises 170 surveys of medium to large terrestrial mammals using camera traps conducted in 144 areas by 74 studies, covering six vegetation types of tropical and subtropical Atlantic Forest of South America (Brazil and Argentina), and present data on species composition and richness. The complete dataset comprises 53,438 independent records of 83 species of mammals, includes 10 species of marsupials, 15 rodents, 20 carnivores, eight ungulates and six armadillos. Species richness averaged 13 species (±6.07 SD ) per site. Only six species occurred in more than 50% of the sites: the domestic dog Canis familiaris , crab‐eating fox Cerdocyon thous , tayra Eira barbara , south American coati Nasua nasua , crab‐eating raccoon Procyon cancrivorus and the nine‐banded armadillo Dasypus novemcinctus . The information contained in this dataset can be used to understand macroecological patterns of biodiversity, community, and population structure, but also to evaluate the ecological consequences of fragmentation, defaunation, and trophic interactions.

Development and validation of a standard area diagram set for assessment of peach rust - Marcos Antônio DOLINSKI; Henrique da Silva Silveira DUARTE; Jéssica Bizarro da SILVA; Louise Larissa May De Mio (European Journal of Plant Pathology, 2017)

Helminthiasis characterization and anthelmintic efficacy for ewes and lambs raised in tropical semiarid region - Gabriela Almeida Bastos; Leydiana Duarte Fonseca; Adriano Vinícius de Paiva Ferreira; Marco Aurélio Morais Soares Costa; Maria Luiza França Silva; Viviane de Oliveira Vasconcelos; Rogério Marcos de Sousa; Eduardo Robson Duarte (Tropical Animal Health and Production, 2017)

Fusarium verticillioides and fumonisin contamination in Bt and non-Bt maize cultivated in Brazil - Vinícius M. Barroso; Liliana O. Rocha; Tatiana A. Reis; Gabriela M. Reis; Aildson P. Duarte; Marcos D. Michelotto; Benedito Correa (Mycotoxin Research, 2017)

Weight, body condition, milk production, and metabolism of Nellore cows when their calves are submitted to different supplementation levels - Aline Gomes da Silva; Mário Fonseca Paulino; Lincoln da Silva Amorim; Edenio Detmann; Luciana Navajas Rennó; Márcio de Souza Duarte; Felipe Henrique de Moura; Luciano Prímola de Melo; Paulo Henrique Silva e Paiva; Marcos Rocha Manso; Victor Valério de Carvalho (Tropical Animal Health and Production, 2017)

Music supported therapy promotes motor plasticity in individuals with chronic stroke - P. Ripollés; N. Rojo; J. Grau-Sánchez; J. L. Amengual; E. Càmara; J. Marco-Pallarés; M. Juncadella; L. Vaquero; F. Rubio; E. Duarte; C. Garrido; E. Altenmüller; et al. (Brain Imaging and Behavior, 2016)

Energy and protein requirements of young Holstein calves in tropical condition - João Paulo Pacheco Rodrigues; Jessika Carolina Moutinho Lima; Marcelo Messias Duarte Castro; Sebastião de Campos Valadares Filho; Mariana Magalhães Campos; Mário Luiz Chizzotti; Marcos Inácio Marcondes (Tropical Animal Health and Production, 2016)

Biomineralization changes with food supply confer juvenile scallops ( Argopecten purpuratus ) resistance to ocean acidification - Laura Ramajo; Núria Marbà; Luis Prado; Sophie Peron; Marco A. Lardies; Alejandro B. Rodriguez‐Navarro; Cristian A. Vargas; Nelson A. Lagos; Carlos M. Duarte (Global Change Biology, 2016)
Future ocean acidification ( OA ) will affect physiological traits of marine species, with calcifying species being particularly vulnerable. As OA entails high energy demands, particularly during the rapid juvenile growth phase, food supply may play a key role in the response of marine organisms to OA . We experimentally evaluated the role of food supply in modulating physiological responses and biomineralization processes in juveniles of the Chilean scallop, Argopecten purpuratus, that were exposed to control ( pH ~ 8.0) and low pH ( pH ~ 7.6) conditions using three food supply treatments (high, intermediate, and low). We found that pH and food levels had additive effects on the physiological response of the juvenile scallops. Metabolic rates, shell growth, net calcification, and ingestion rates increased significantly at low pH conditions, independent of food. These physiological responses increased significantly in organisms exposed to intermediate and high levels of food supply. Hence, food supply seems to play a major role modulating organismal response by providing the energetic means to bolster the physiological response of OA stress. On the contrary, the relative expression of chitin synthase, a functional molecule for biomineralization, increased significantly in scallops exposed to low food supply and low pH , which resulted in a thicker periostracum enriched with chitin polysaccharides. Under reduced food and low pH conditions, the adaptive organismal response was to trade‐off growth for the expression of biomineralization molecules and altering of the organic composition of shell periostracum, suggesting that the future performance of these calcifiers will depend on the trajectories of both OA and food supply. Thus, incorporating a suite of traits and multiple stressors in future studies of the adaptive organismal response may provide key insights on OA impacts on marine calcifiers.

Nutritional and productive performance of dairy cows fed corn silage or sugarcane silage with or without additives - Felipe Leite de Andrade; João Paulo Pacheco Rodrigues; Edenio Detmann; Sebastião de Campos Valadares Filho; Marcelo Messias Duarte Castro; Aline Souza Trece; Tadeu Eder Silva; Vivian Fischer; Kirsten Weiss; Marcos Inácio Marcondes (Tropical Animal Health and Production, 2016)

A global meta‐analysis of the relative extent of intraspecific trait variation in plant communities - Andrew Siefert; Cyrille Violle; Loïc Chalmandrier; Cécile H. Albert; Adrien Taudiere; Alex Fajardo; Lonnie W. Aarssen; Christopher Baraloto; Marcos B. Carlucci; Marcus V. Cianciaruso; Vinícius de L. Dantas; Francesco de Bello; et al. (Ecology Letters, 2015)
Recent studies have shown that accounting for intraspecific trait variation ( ITV ) may better address major questions in community ecology. However, a general picture of the relative extent of ITV compared to interspecific trait variation in plant communities is still missing. Here, we conducted a meta‐analysis of the relative extent of ITV within and among plant communities worldwide, using a data set encompassing 629 communities (plots) and 36 functional traits. Overall, ITV accounted for 25% of the total trait variation within communities and 32% of the total trait variation among communities on average. The relative extent of ITV tended to be greater for whole‐plant (e.g. plant height) vs. organ‐level traits and for leaf chemical (e.g. leaf N and P concentration) vs. leaf morphological (e.g. leaf area and thickness) traits. The relative amount of ITV decreased with increasing species richness and spatial extent, but did not vary with plant growth form or climate. These results highlight global patterns in the relative importance of ITV in plant communities, providing practical guidelines for when researchers should include ITV in trait‐based community and ecosystem studies.

Effects of resistance training on neuromuscular characteristics and pacing during 10-km running time trial - Mayara V. Damasceno; Adriano E. Lima-Silva; Leonardo A. Pasqua; Valmor Tricoli; Marcos Duarte; David J. Bishop; Rômulo Bertuzzi (European Journal of Applied Physiology, 2015)

CO2-Driven Ocean Acidification Disrupts the Filter Feeding Behavior in Chilean Gastropod and Bivalve Species from Different Geographic Localities - Cristian A. Vargas; Victor M. Aguilera; Valeska San Martín; Patricio H. Manríquez; Jorge M. Navarro; Cristian Duarte; Rodrigo Torres; Marco A. Lardies; Nelson A. Lagos (Estuaries and Coasts, 2015)

Pattern of multiresistant to antimicrobials and heavy metal tolerance in bacteria isolated from sewage sludge samples from a composting process at a recycling plant in southern Brazil - Karina Heck; Évilin Giordana De Marco; Mariana Wanderlei Duarte; Sabrina Pinto Salamoni; Sueli Van Der Sand (Environmental Monitoring and Assessment, 2015)

Intraspecific Variability in the Response of the Edible Mussel Mytilus chilensis (Hupe) to Ocean Acidification - Cristian Duarte; Jorge M. Navarro; Karin Acuña; Rodrigo Torres; Patricio H. Manríquez; Marcos A. Lardies; Cristian A. Vargas; Nelson A. Lagos; Víctor Aguilera (Estuaries and Coasts, 2015)

Glycolipid Sensing and Innate Immunity in Paracoccidioidomycosis - Vanessa G. Batista; Marcos S. Toledo; Anita H. Straus; Maria J. S. Mendes-Giannini; Alberto J. S. Duarte; Helio K. Takahashi; Gil Benard (Mycopathologia, 2014)

Determination of Monoaromatic Hydrocarbons (BTEX) in Surface Waters from a Brazilian Subtropical Hydrographic Basin - Andreia Neves Fernandes; Cindy Duarte Gouveia; Marco Tadeu Grassi; Janaina da Silva Crespo; Marcelo Giovanela (Bulletin of Environmental Contamination and Toxicology, 2014)

Economical and financial analysis of lamb finishing fed with diets formulated according to the NRC (1985) and the NRC (2007) - Marcos Cláudio Pinheiro Rogério; Eliane Minervina de Castro; Espedito Cezário Martins; Jomar Patrício Monteiro; Kleibe de Moraes Silva; Magno José Duarte Cândido; Tereza Cristina Lacerda Gomes; Antoine Francis Roux Bloc; Ângela Maria de Vasconcelos; Eneas Reis Leite; Hélio Henrique Araújo Costa (Tropical Animal Health and Production, 2012)

Expressed sequence-tag analysis of ovaries of Brachiaria brizantha reveals genes associated with the early steps of embryo sac differentiation of apomictic plants - Érica Duarte Silveira; Larissa Arrais Guimarães; Diva Maria de Alencar Dusi; Felipe Rodrigues da Silva; Natália Florencio Martins; Marcos Mota do Carmo Costa; Márcio Alves-Ferreira; Vera Tavares de Campos Carneiro (Plant Cell Reports, 2012)

Can amphibians take the heat? Vulnerability to climate warming in subtropical and temperate larval amphibian communities - Helder Duarte; Miguel Tejedo; Marco Katzenberger; Federico Marangoni; Diego Baldo; Juan Francisco Beltrán; Dardo Andrea Martí; Alex Richter‐Boix; Alejandro Gonzalez‐Voyer (Global Change Biology, 2012)
Predicting the biodiversity impacts of global warming implies that we know where and with what magnitude these impacts will be encountered. Amphibians are currently the most threatened vertebrates, mainly due to habitat loss and to emerging infectious diseases. Global warming may further exacerbate their decline in the near future, although the impact might vary geographically. We predicted that subtropical amphibians should be relatively susceptible to warming‐induced extinctions because their upper critical thermal limits ( CT max ) might be only slightly higher than maximum pond temperatures ( T max ). We tested this prediction by measuring CT max and T max for 47 larval amphibian species from two thermally distinct subtropical communities (the warm community of the Gran Chaco and the cool community of Atlantic Forest, northern Argentina), as well as from one European temperate community. Upper thermal tolerances of tadpoles were positively correlated (controlling for phylogeny) with maximum pond temperatures, although the slope was steeper in subtropical than in temperate species. CT max values were lowest in temperate species and highest in the subtropical warm community, which paradoxically, had very low warming tolerance ( CT max – T max ) and therefore may be prone to future local extinction from acute thermal stress if rising pond T max soon exceeds their CT max . Canopy‐protected subtropical cool species have larger warming tolerance and thus should be less impacted by peak temperatures. Temperate species are relatively secure to warming impacts, except for late breeders with low thermal tolerance, which may be exposed to physiological thermal stress in the coming years.

Development and Evaluation of a Floating Multiparticulate Gastroretentive System for Modified Release of AZT - Valquíria Miwa Hanai Yoshida; José Martins de Oliveira Junior; Marcos Moisés Gonçalves; Marta Maria Duarte Carvalho Vila; Marco Vinícius Chaud (AAPS PharmSciTech, 2011)

Antarctic krill as a source of dissolved organic carbon to the Antarctic ecosystem - Sergio Ruiz-Halpern; Carlos M. Duarte; Antonio Tovar-Sanchez; Marcos Pastor; Burkhard Horstkotte; Sebastien Lasternas; Susana Agustí (Limnology and Oceanography, 2011)
The role of krill as a source of dissolved organic matter in the Southern Ocean was tested through a series of experiments performed around the Antarctic Peninsula. These experiments revealed high but variable release rates of dissolved material (carbon and nutrients), supplying, on average, 150 mmol dissolved organic carbon (DOC) m −2 d −1 , which is comparable with that supported by phytoplankton. Krill support, on average, 73% of the combined krill + phytoplankton production of DOC in the ecosystem, implying the importance of krill in conditioning the productivity of the Southern Ocean. However, the contribution of krill as a source of DOC varied greatly because of the patchy distribution of both krill and primary producers in the region, ranging from 98% to 10% of the combined (krill + phytoplankton) DOC release rates. These results suggest that rapid decline in krill standing stocks associated with reduced ice cover may have major consequences for microbial communities in the ecosystem, since bacterial carbon demand often exceeds the DOC supplied by phytoplankton in coastal areas of the Southern Ocean, with potential unforeseen consequences in the carbon balance of the Southern Ocean.

Macroecological analyses reveal historical factors influencing seed dispersal strategies in Brazilian Araucaria forests - Leandro da S. Duarte; Marcos B. Carlucci; Valério D. Pillar (Global Ecology and Biogeography, 2009)
Aim Our objective was to evaluate the influence of distinct macroecological factors (space, floristics and environment) on the variation in seed dispersal strategies of shrubs and trees in the Araucaria forest biome in the southern and south‐eastern Brazilian highlands. We hypothesize that history‐related factors (space, floristics) are major determinants of the proportion of endo‐ and syn‐zoochorous species in Araucaria forests, despite the current gradients in environmental conditions. Location Araucaria forest is the main forest biome in southern Brazil, at altitudes above 500 m a.s.l. (latitude ≤ 30° S). Their northern limit in Brazil is at latitude 20° S, where forests occur at elevations above 1000 m a.s.l. Methods We compiled information from 27 floristic checklists comprising shrub and tree species distributed along the geographical range of the Brazilian Araucaria forest biome. We classified species as zoochorous and non‐zoochorous, based on morphological attributes of their diaspores. Sites were described by geographical coordinates (latitude, longitude) and five environmental variables. We evaluated separately the influence of floristic, spatial and environmental variables on zoochory using correspondence analysis and linear regressions. Further, we evaluated causal connections between these variable groups using Mantel tests and path analysis. Results Zoochory increased with both latitude and longitude. Regression analysis showed that rainfall seasonality was the only environmental variable explaining the variation in the proportion of zoochorous species. All pairwise Mantel correlations between space, rainfall seasonality, floristics and zoochory were significant. Path analysis showed that rainfall seasonality was strongly determined by spatial distances between sites, and floristics was directly determined by rainfall seasonality. Further zoochory was mostly determined by floristics. Main conclusions Taking into account historical factors in the interpretation of macroecological patterns improves our understanding of biodiversity gradients. Hypotheses based on long‐term dynamics of distinct floristic groups provide some useful insights into patterns shown by studies elsewhere. Here we offer an analytical solution to incorporate history‐related factors into macroecological analyses. While history‐based hypotheses do not replace any other ideas concerning macroecological patterns, they are likely to improve our understanding on factors determining present‐day ecological patterns.

Lap4, a vacuolar aminopeptidase I, is involved in cadmium-glutathione metabolism - Paula D. B. Adamis; Sergio C. Mannarino; Cristiano J. Riger; Giselle Duarte; Ana Cruz; Marcos D. Pereira; Elis C. A. Eleutherio (BioMetals, 2009)

Complexity of human postural control in young and older adults during prolonged standing - Marcos Duarte; Dagmar Sternad (Experimental Brain Research, 2008)

Effects of postural task requirements on the speed–accuracy trade-off - Marcos Duarte; Mark L. Latash (Experimental Brain Research, 2007)

Effect of load level and muscle pain intensity on the motor control of elbow-flexion movements - Ulysses Fernandes Ervilha; Lars Arendt-Nielsen; Marcos Duarte; Thomas Graven-Nielsen (European Journal of Applied Physiology, 2004)

The effect of muscle pain on elbow flexion and coactivation tasks - Ulysses F. Ervilha; Lars Arendt-Nielsen; Marcos Duarte; Thomas Graven-Nielsen (Experimental Brain Research, 2004)

Movement sway: changes in postural sway during voluntary shifts of the center of pressure - Mark L. Latash; Sandra S. Ferreira; Silvana A. Wieczorek; Marcos Duarte (Experimental Brain Research, 2003)

Effects of body lean and visual information on the equilibrium maintenance during stance - Marcos Duarte; Vladimir M. Zatsiorsky (Experimental Brain Research, 2002)

Analysis of kinematically redundant reaching movements using the equilibrium-point hypothesis - Paola Cesari; Takako Shiratori; Paolo Olivato; Marcos Duarte (Biological Cybernetics, 2001)

Putative association of a mutant ROM1 allele with retinitis pigmentosa - Amalia Martínez-Mir; Concha Vilela; Mònica Bayés; Diana Valverde; L. Dain; Magdalena Beneyto; Marina Marco; Montserrat Baiget; Daniel Grinberg; Susana Balcells; Roser Gonzàlez-Duarte; Lluïsa Vilageliu (Human Genetics, 1997)